Transparent thermoplastic polyurethane elastomer and preparation method thereof
Through the combination of polyether polyol and polyester polyol and aliphatic isocyanate, the preparation process is optimized, and the technical difficulties of transparent polyurethane elastomers are solved in taking into account both light transmittance and mechanical strength, and the high transparency and high strength of the material are achieved .
Patent Information
- Application Number
- CN202411650226.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When existing transparent polyurethane elastomers take into account both high light transmittance and high mechanical strength, the mechanical strength of the material decreases, making it difficult to achieve the technical difficulties of taking into account both.
Polyether polyol and polyester polyol are combined as two-component soft chain segments, combined with aliphatic isocyanate and 1,4-butanediol as hard chain segments, improve compatibility through optimized preparation process, and the synthesis has mechanical properties and Optical transparent thermoplastic polyurethane elastomer.
The mechanical properties and optical transparency of polyurethane elastomers are achieved, and the comprehensive performance of the material is improved.
Smart Images

Figure CN119161555A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermoplastic polyurethane elastomers and relates to a transparent thermoplastic polyurethane elastomer and a preparation method thereof. Background Art
[0002] Thermoplastic polyurethane elastomer, also known as thermoplastic polyurethane rubber, is a (AB) n A block linear polymer, A is a polyester or polyether with a high molecular weight (1000~6000), B is a diol containing 2~12 straight-chain carbon atoms, and the chemical structure between the AB segments is diisocyanate. Thermoplastic polyurethane rubber relies on intermolecular hydrogen bond crosslinking or light crosslinking between macromolecular chains. These two crosslinking structures are reversible as the temperature rises or falls. In the molten state or solution state, the intermolecular force is weakened, and after cooling or solvent evaporation, there are strong intermolecular forces connecting together, restoring the original solid properties. Polyurethane elastomers are widely used in footwear, sports equipment, automobiles, construction, furniture and other fields because of their excellent tensile strength, tear strength, impact resistance, wear resistance, weather resistance, hydrolysis resistance and oil resistance.
[0003] Transparent polyurethane elastomer is a special polyurethane elastomer with a certain optical transparency. Its optical transparency comes from inhibiting the size of the hard segment phase and the growth of crystals, as well as good light stability. This material is clear and transparent, has high tensile strength and good energy absorption. In recent years, its application in optical equipment, high-end building materials and safety protection has been continuously expanding, and high-performance transparent polyurethane elastomers have received more and more attention. However, due to its special application field, it is often required to have both high light transmittance and high mechanical strength. To obtain a transparent polyurethane elastomer material, the crystallinity of the material must be destroyed, but this will lead to a decrease in the mechanical strength of the material. Therefore, how to balance light transmittance and mechanical strength is a technical problem that needs to be solved urgently. Summary of the invention
[0004] In view of the deficiencies in the prior art, the purpose of the present invention is to provide a transparent grade thermoplastic polyurethane elastomer and a preparation method thereof, wherein a polyether polyol and a polyester polyol are compounded as a two-component soft segment, and aliphatic isocyanate and 1,4-butanediol are used as a hard segment. The preparation process of the polyether polyol and the polyester polyol is optimized and adjusted, and the compatibility of the two is improved by changing the ratio and structure of the two, thereby giving full play to the respective performance advantages of the two, and synthesizing a thermoplastic polyurethane elastomer with both mechanical properties and optical transparency.
[0005] To achieve this object, the present invention adopts the following technical solutions: In a first aspect, the present invention provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, the preparation method comprising: Step (I), mixing castor oil, bisphenol A and potassium hydroxide uniformly to obtain a polyether raw material solution, adding the polyether raw material solution into a polymerization reactor, replacing the polymerization reactor with nitrogen and decompressing and dehydrating the polyether raw material solution by nitrogen bubbling, then adjusting the temperature and pressure in the polymerization reactor, adding propylene oxide to the polyether raw material solution, stirring and heating to induce a reaction, and obtaining a polyether polyol oligomer; adding a cyanide complex and a phosphoric acid solution to the polyether polyol oligomer, mixing uniformly to obtain an intermediate solution; adjusting the temperature and pressure in the polymerization reactor, adding propylene oxide and ethylene oxide to the intermediate solution, stirring and heating to perform a polymerization reaction, and obtaining a polyether polyol; Step (II), glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol are mixed uniformly to obtain a polyester raw material solution, the polyester raw material solution is added to an esterification reaction kettle, the esterification reaction kettle is replaced with nitrogen, and then the polyester raw material solution is stirred and heated to cause an esterification reaction; after the esterification reaction is completed, the esterification product obtained by the reaction is transferred to a polycondensation reaction kettle, dibutyltin dilaurate is added to the esterification product, and the mixture is stirred and heated to cause a polycondensation reaction, and a polyester polyol is obtained after the reaction is completed; Step (III), the polyether polyol prepared in step (I) and the polyester polyol prepared in step (II) are mixed evenly, and dehydrated under vacuum and heating conditions to obtain component A; aliphatic isocyanate is used as component B; the dehydrated 1,4-butanediol and a tertiary amine catalyst are mixed evenly to obtain component C; the component A, the component B and the component C are mixed evenly and then injected into a mold, demolded after cooling, and finally heated and vulcanized to obtain a transparent grade thermoplastic polyurethane elastomer.
[0006] Polyols used to synthesize the soft segments of transparent thermoplastic polyurethane elastomers include polyester polyols and polyether polyols. Polyurethane elastomers synthesized with polyester polyols as raw materials are called polyester-type polyurethane elastomers, and polyurethane elastomers synthesized with polyether polyols as raw materials are called polyether-type polyurethane elastomers. Compared with polyether-type polyurethane elastomers, polyester-type polyurethane elastomers have higher strength and hardness, which is attributed to the higher polarity and cohesive energy of the ester group, which makes the intermolecular force of the soft segments composed of polyester polyols greater, and can produce hydrogen bonds with the hard segments, thereby significantly enhancing the strength and hardness of polyester-type polyurethane elastomers. However, due to the poor flexibility of the polyester polyol molecular chain, the heat generation of the polyester polyurethane elastomer will be higher under the action of external alternating stress, while polyether polyols contain ether bonds, the molecular chain motion potential energy is low, and the flexibility is good. Even at lower temperatures, the polyurethane elastomer can still maintain good elasticity, and it has excellent hydrolysis resistance and low internal friction under dynamic conditions.
[0007] In addition, the optical transparency of polyether polyurethane elastomer is better than that of polyester polyurethane elastomer. This is because crystallization will seriously affect the optical transparency of polyurethane elastomer. According to polymer structure theory, only random amorphous polymers can be transparent. However, due to the existence of crystalline and amorphous regions in crystalline copolymers, the refractive index of light to the crystalline and amorphous regions is different, which leads to low optical transparency of crystalline copolymers. For polyurethane elastomers, the crystallization of any phase in the soft segment and the hard segment will have an adverse effect on its optical transparency. In polyester polyols, due to the high polarity of the ester group, crystallization is easy to occur, while the interaction force between the molecular chains of polyether polyols is weak, and random arrangement is easy, the crystallinity is low, and the optical transparency is good. Therefore, the optical transparency of polyether polyurethane elastomer is better than that of polyester polyurethane elastomer.
[0008] In order to balance the mechanical properties and optical transparency of polyurethane elastomer, the present invention uses polyether polyol and polyester polyol as two-component soft segments, and aliphatic isocyanate and 1,4-butanediol as hard segments to synthesize thermoplastic polyurethane elastomer with both mechanical properties and optical transparency. Since the ether bond in polyether polyol is a non-polar bond, and the ester bond in polyester polyol is a polar bond, the polarity difference of the two polyols is large, and the compatibility is poor. The incompatibility between polyether polyol and polyester polyol and between polyol and hard segment increases the microphase separation degree of polyurethane elastomer, thereby reducing the miscibility between soft segment and hard segment, which is beneficial to the crystallization of soft segment, and is manifested as the enhancement of mechanical properties in macroscopic terms, but is extremely unfavorable to the optical transparency of polyurethane elastomer. For this reason, the present invention optimizes and adjusts the preparation process of polyether polyol and polyester polyol, and improves the compatibility of the two by changing the ratio and structure of the two, so as to give full play to the performance advantages of the two, and obtain a polyurethane elastomer with excellent comprehensive performance.
[0009] In the process of synthesizing polyether polyols, the present invention firstly uses castor oil containing active hydrogen and bisphenol A as initiators, and obtains polyether polyol oligomers through the ring-opening self-polymerization reaction of ethylene oxide under the action of an alkali catalyst; then, under the catalytic action of a cyanide complex, ethylene oxide and propylene oxide are subjected to ring-opening polymerization to end-cap the polyether polyol oligomers, thereby obtaining a polyether polyol with a primary hydroxyl group at the end and having high reaction activity.
[0010] The present invention specifically selects bisphenol A as the initiator because bisphenol A has a double benzene ring molecular structure, and the polyether polyol synthesized with bisphenol A as the skeleton structure can give the polyurethane elastomer excellent rigidity and toughness; in addition, the polyether polyol synthesized with bisphenol A polyether has good compatibility with polyester polyol.
[0011] The present invention uses ethylene oxide and propylene oxide to compound as a composite end-capping agent. This is because the ring-opening polymerization of ethylene oxide generates a primary hydroxyl compound, and the ring-opening polymerization of propylene oxide generates a secondary hydroxyl compound. The activity of the primary hydroxyl group in reacting with the isocyanate group is much higher than that of the secondary hydroxyl group. Therefore, when the polyether polyol formed by the polymerization of propylene oxide is used to synthesize the polyurethane elastomer, the processing time will be prolonged, the energy consumption will increase, and the process cost will increase. For this reason, the present invention adds ethylene oxide during the synthesis process of the polyether polyol, and the polyether polyol is end-capped by ethylene oxide, thereby introducing a primary hydroxyl group on the hydroxyl group at the end of the polyether polyol, which can improve the reactivity of the polyether polyol. However, when only ethylene oxide is added to cap the polyether polyol, a multiphase blend consisting of uncapped polyether polyol (with secondary hydroxyl groups at the ends), polyethylene glycol and a small amount of polyether polyol with a high capping rate is obtained. This is because the chain growth rate of ethylene oxide self-polymerization is higher than the chain transfer rate of ethylene oxide to secondary hydroxyl groups, resulting in a large amount of ethylene oxide self-polymerizing to form polyethylene glycol, and only a small amount of ethylene oxide has a capping effect on the polyether polyol, which ultimately causes the selectivity of the target product to decrease. Therefore, in the present invention, when synthesizing polyether polyols by catalysis of a cyanide complex (DMC), a composite of propylene oxide and ethylene oxide is used as a capping agent.
[0012] The present invention adopts DMC as a catalyst for the ring-opening polymerization reaction of propylene oxide and ethylene oxide. The catalytic mechanism of DMC belongs to weak cationic coordination polymerization, including three parts of chain initiation, chain growth and chain transfer. During the reaction process, DMC can provide active sites so that the chains of polyether polyol oligomers are connected to each active site. At this time, the polymerization monomers propylene oxide and ethylene oxide will be inserted into the vacant sites provided by the active center for ring-opening polymerization, thereby realizing the chain growth of the copolymer. Due to its special coordination structure, when participating in the ring-opening polymerization reaction of propylene oxide and ethylene oxide, it has the advantages of less side reactions, short reaction cycle, less dosage, etc., and can greatly shorten the reaction time; at the same time, the polyether polyol synthesized by DMC catalysis has the characteristics of low unsaturation, high activity, high molecular weight, narrow molecular weight distribution, low acid value, etc.
[0013] During the prepolymerization of propylene oxide, potassium hydroxide is added as a catalyst, making the reaction system alkaline. Excessive alkalinity will affect the catalytic activity of DMC. To avoid the inactivation of DMC, the present invention adds an acidic neutralizer to the reaction system before the copolymerization of propylene oxide and ethylene oxide to adjust the pH value of the reaction system to acidic. DMC has a high catalytic activity under acidic conditions, and the copolymerization time can be shortened after adding the acidic neutralizer. Common acidic neutralizers include sulfuric acid, phosphoric acid, and oxalic acid. The salts formed by them and potassium hydroxide have low solubility in polyether polyols and will be filtered and separated in the form of crystals after dehydration. When an organic acid (such as oxalic acid) is used for alkali neutralization, although its acidity is weak and has no obvious corrosiveness, its water solubility is poor. If it is directly added to the reaction system, the neutralization effect on potassium hydroxide is poor, and the crystal particles of the generated organic metal salt are small, which is difficult to filter, and the purpose of efficient separation cannot be achieved. In addition, sulfuric acid is too acidic and can easily cause the decomposition of polyether polyols, resulting in yellowing of the color of the final synthesized polyurethane elastomer. Moreover, sulfuric acid is severely corrosive to equipment, so the dosage needs to be strictly controlled when used, and it is not a preferred acidic neutralizer. The present invention specifically selects phosphoric acid as an acidic neutralizer because the hydrogen in phosphoric acid is more active when reacting with DMC, making the copolymerization reaction rate of propylene oxide and ethylene oxide faster, and a slightly excessive amount of phosphoric acid has little effect on the physical and chemical indicators such as color, transparency, and mechanical properties of the final synthesized polyurethane elastomer.
[0014] The synthesis of polyester polyols begins with the esterification reaction of polyols and polyacids. In this process, the hydroxyl groups (-OH) of the polyols and the carboxyl groups (-COOH) of the polyacids undergo an esterification reaction under heating and in the presence of a catalyst to generate ester groups (-COO-) and water. As the reaction continues, the hydroxyl and carboxyl groups in the system gradually decrease, while the ester groups gradually increase. Based on the esterification reaction, as the reaction proceeds further, the ester groups and hydroxyl groups between molecules will also undergo a condensation reaction to form a longer molecular chain, namely a polyester chain. This process is a polycondensation reaction.
[0015] The optical transparency of polyurethane elastomers mainly depends on the crystallization performance of the soft segment. Polyurethane elastomers synthesized using only polyester polyols contain highly polar ester groups, which make them easy to crystallize, affecting the optical transparency of polyurethane elastomers. Therefore, in order to take into account both the optical transparency and mechanical properties of polyurethane elastomers, it is necessary to control the crystallinity of polyester polyols, thereby controlling the crystallinity of polyurethane elastomers and ultimately obtaining polyurethane elastomers with high transparency.
[0016] In the selection of polyols, the present invention specifically selects 1,3-propylene glycol and 1,2-propylene glycol as alcohol raw materials for polyester polyols. Among them, the molecular chain structure of 1,3-propylene glycol is symmetrical and has no side groups. It is easy to form hydrogen bonds between molecules and is easy to crystallize, which is beneficial to improving the mechanical properties of polyurethane elastomers. The molecular chain structure of 1,2-propylene glycol is asymmetrical and has side groups. The side groups will weaken the force between molecules and make it difficult to crystallize, which is beneficial to improving the optical transparency of polyurethane elastomers.
[0017] There are many types of catalysts used in the synthesis of polyester polyols, and the more common ones are peptide catalysts, organotin catalysts and tertiary amine catalysts. Compared with peptide catalysts and organotin catalysts, tertiary amine catalysts have poor catalytic reaction activity for -NCO and -OH. Peptide catalysts are easily decomposed when exposed to water during the synthesis of polyester polyols, and titanium compounds react with hydroxyl compounds to form Ti-OC (Ar) structures, causing the conjugated system of aromatic ring electron clouds to increase, resulting in enhanced absorption intensity in the visible light region of the ultraviolet absorption spectrum, causing polyether polyols to easily turn yellow, and ultimately reducing the optical transparency of polyurethane elastomers. Therefore, the present invention uses an organotin catalyst dibutyltin dilaurate as a catalyst for synthesizing polyester polyols.
[0018] The aggregate structure of polyurethane elastomer includes hard segments, soft segments and interface layers. Among them, polyether polyols and polyester polyols form soft segments, and isocyanates and small molecule chain extenders are cross-linked with soft segments as hard segments to form block structures. The hard segments of polyurethane are composed of chain extenders and polyisocyanates. The content and structure of the hard segments directly determine the mechanical properties and optical transparency of polyurethane elastomers.
[0019] Commonly used polyisocyanates include aromatic isocyanates and aliphatic isocyanates. The present invention specifically selects aliphatic isocyanates as hard segments. This is because aromatic isocyanates are easy to produce orderly arrangement and crystallization under hydrogen bonds and intermolecular forces due to the presence of benzene rings, which affects the optical transparency of polyurethane elastomers. Chain extenders are also one of the important factors affecting the optical transparency of polyurethane elastomers. Small molecular compounds containing hydroxyl or amine groups play a role in chain extension and cross-linking in polyurethane elastomers, which affects the relationship between the soft and hard segments of polyurethane elastomers, thereby directly affecting the optical transparency of polyurethane elastomers. When small molecular polyamine substances are used as chain extenders, due to the introduction of strongly polar urea groups, the secondary amino groups on the urea groups can form a three-dimensional hydrogen bond structure with the urea carbonyl group, so that the hard segments have a higher affinity, which is conducive to the aggregation and crystallization of the hard segments, and promotes the two-phase separation of the hard segments and the soft segments, so that the optical transparency of the prepared polyurethane elastomer is reduced. When a small molecule polyol is used as a chain extender, the small molecule polyol does not contain a strong polar bond and is easy to synthesize a polyurethane elastomer with high optical transparency.
[0020] As a preferred technical solution of the present invention, in step (I), the mass ratio of the castor oil, the bisphenol A and the potassium hydroxide is 100:(50-60):(1.2-1.5), for example, it can be 100:50:1.2, 100:51:1.25, 100:52:1.3, 100:53:1.35, 100:54:1.4, 100:55:1.45, 100:56:1.5, 100:57:1.2, 100:58:1.3, 100:59:1.4 or 100:60:1.5, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0021] In some optional examples, the operation process of nitrogen replacement of the polymerization reactor includes: 90~100Nm 3 Nitrogen is introduced into the polymerization reactor at a flow rate of 90 Nm / h until the oxygen content in the polymerization reactor is ≤50 ppm, for example, 90 Nm / h. 3 / h、91Nm 3 / h、92Nm 3 / h、93Nm 3 / h、94Nm 3 / h、95Nm 3 / h、96Nm 3 / h、97Nm 3 / h、98Nm 3 / h、99Nm 3 / h or 100Nm 3 / h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] In some optional examples, the operation process of nitrogen bubbling and decompression dehydration of the polyether raw material solution includes: The polyether raw material solution is heated to a dehydration temperature, and nitrogen is bubbled into the polyether raw material solution from the bottom of the polymerization reactor, and the polymerization reactor is evacuated to a negative pressure to perform nitrogen bubbling decompression dehydration.
[0023] In some optional embodiments, the dehydration temperature is 100-110°C, for example, it can be 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0024] In some optional embodiments, the flow rate of nitrogen gas injected into the polyether raw material solution is 60-80 Nm 3 / h, for example, it can be 60Nm 3 / h、62Nm 3 / h、64Nm 3 / h、66Nm 3 / h、68Nm 3 / h、70Nm 3 / h、72Nm 3 / h、74Nm 3 / h、76Nm 3 / h、78Nm 3 / h or 80Nm 3 / h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0025] In some optional examples, the vacuum degree in the polymerization reactor after evacuation is controlled at -0.09~-0.1MPa, for example, it can be -0.09MPa, -0.091MPa, -0.092MPa, -0.093MPa, -0.094MPa, -0.095MPa, -0.096MPa, -0.097MPa, -0.098MPa, -0.099MPa or -0.1MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] In some optional examples, the time for nitrogen bubbling reduced pressure dehydration is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In the reaction process of synthesizing polyether polyols using DMC as a catalyst, if a small amount of water is contained in the reaction system, the selectivity of DMC will be reduced, a large number of side reactions will occur, resulting in a decrease in the catalytic activity of DMC, a prolonged polymerization reaction time, and a serious impact on the polymerization reaction efficiency of propylene oxide. It will also affect the color of the product, resulting in a decrease in the optical transparency of the polyurethane elastomer. Therefore, before the reaction, the catalyst and the raw material must be dehydrated. In the present invention, the polyether raw material solution is heated and heated under nitrogen bubbling conditions and dehydrated by vacuuming.
[0028] The present invention particularly limits the time of nitrogen bubbling decompression dehydration to 1-2 hours. The dehydration time is inversely proportional to the time of the induction reaction. The longer the dehydration time, the shorter the time of the induction reaction and the faster the reaction rate. Therefore, the dehydration time cannot be too low. However, as the dehydration time is prolonged, the induction reaction rate and product quality are not significantly improved, but the energy consumption is increased. At the same time, it is also very easy to cause the color of the prepared polyether polyol to deepen. Therefore, the dehydration time of the polyether raw material solution must be strictly controlled within the range of 1-2 hours.
[0029] In some optional examples, the water content of the polyether raw material solution after nitrogen bubbling and reduced pressure dehydration is ≤0.15%, for example, it can be 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14% or 0.15%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] As a preferred technical solution of the present invention, in step (I), before adding propylene oxide to the polyether raw material solution, the temperature in the polymerization reactor is adjusted to 90-100°C, for example, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0031] In some optional examples, before adding propylene oxide to the polyether raw material solution, the pressure in the polymerization reactor is adjusted to 0.18~0.23MPa, for example, it can be 0.18MPa, 0.185MPa, 0.19MPa, 0.195MPa, 0.20MPa, 0.205MPa, 0.21MPa, 0.215MPa, 0.22MPa, 0.225MPa or 0.23MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] In some optional examples, the ratio of the total mass of castor oil and bisphenol A in the polyether raw material solution to the mass of the propylene oxide is (8-10):1, for example, it can be 8.0:1, 8.2:1, 8.4:1, 8.6:1, 8.8:1, 9.0:1, 9.2:1, 9.4:1, 9.6:1, 9.8:1 or 10.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] The present invention specifically defines the mass ratio of the initiator (castor oil and bisphenol A) in the polyether raw material solution to the mass ratio of propylene oxide to (8-10):1. When the amount of propylene oxide is lower than the lower limit of the range defined by the present invention, the concentration of the propylene oxide monomer that triggers the induction reaction is too low, the self-polymerization reaction of the propylene oxide monomer is difficult to proceed, the induction reaction time is too long, and the risk of catalyst poisoning and deactivation increases. When the amount of propylene oxide exceeds the upper limit of the range defined by the present invention, the induction reaction time is greatly shortened with the increase of the amount of propylene oxide, but due to the excessive amount of propylene oxide, the concentration of the propylene oxide monomer participating in the coordination is too high, the number of propylene oxide monomers activated and participating in the polymerization reaction per unit time increases, the heat released by the reaction increases, and the gasification of propylene oxide and the polymerization reaction are accelerated, resulting in rapid heat release of the reaction. Once the polymerization reaction starts, the subsequent chain reaction will continuously release a large amount of heat. Once the heat released by the reaction is not removed in time, a safety hazard will occur. Taking into account the smooth progress of the polymerization reaction and process safety factors, the present invention specifically limits the mass ratio of the initiator to the mass of propylene oxide to (8-10):1.
[0034] In some optional examples, the operation process of inducing the reaction includes: After adding propylene oxide to the polyether raw material solution, the reaction is kept warm, and then the temperature is increased to the induction temperature at a first heating rate and kept warm for reaction. When the pressure in the polymerization reactor continues to decrease and drops to negative pressure, and the temperature begins to rise continuously, it indicates that the induction reaction is completed and the polyether polyol oligomer is obtained.
[0035] In some optional examples, after adding propylene oxide to the polyether raw material solution, the reaction is kept warm for 0.5 to 1 hour, for example, 0.5h, 0.55h, 0.6h, 0.65h, 0.7h, 0.75h, 0.8h, 0.85h, 0.9h or 1h, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] In some optional instances, the first heating rate is 1~3℃ / min, for example, it can be 1.0℃ / min, 1.2℃ / min, 1.4℃ / min, 1.6℃ / min, 1.8℃ / min, 2.0℃ / min, 2.2℃ / min, 2.4℃ / min, 2.6℃ / min, 2.8℃ / min or 3.0℃ / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0037] In some optional embodiments, the induction temperature is 120-130°C, for example, it can be 120°C, 121°C, 122°C, 123°C, 124°C, 125°C, 126°C, 127°C, 128°C, 129°C or 130°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] The present invention specifically limits the induction temperature to 120-130°C. When the induction temperature is lower than 120°C, the potassium hydroxide catalyst cannot be fully activated, resulting in a long induction reaction time. Increasing the induction temperature can accelerate the induction reaction and greatly shorten the induction reaction time. When the induction temperature is higher than 130°C, the induction reaction will be too intense, which is not conducive to the safe and stable reaction, and is very likely to form ultra-high molecular weight polyether polyols.
[0039] In some optional examples, the reaction is kept at the induction temperature for 2 to 3 hours, for example, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours, 2.5 hours, 2.6 hours, 2.7 hours, 2.8 hours, 2.9 hours or 3.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0040] In some optional examples, the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is 1000:(0.1-0.12):(0.008-0.009), for example, it can be 1000:0.1:0.008, 1000:0.102:0.00 / 1, 1000:0.104:0.0082, 1000:0.106:0.0083, 1000: 0.108:0.0084, 1000:0.11:0.0085, 1000:0.112:0.0086, 1000:0.114:0.0087, 1000:0.116:0.0088, 1000:0.118:0.0089 or 1000:0.12:0.009, but are not limited to the listed values, other unlisted values within the numerical range are also applicable.
[0041] The present invention specifically limits the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution to 1000:(0.1-0.12):(0.008-0.009). With the increase of the amount of DMC catalyst, the polymerization reaction rate of propylene oxide and ethylene oxide increases, the reaction time is shortened, and the reaction is carried out more thoroughly. However, in terms of the performance of the polyether polyol, the amount of DMC catalyst is not the higher the better. On the one hand, the excessive amount of DMC catalyst leads to an increase in production costs, and may also cause the appearance of the obtained polyether polyol to be pink, thereby affecting the appearance color and transparency of the subsequently synthesized polyurethane elastomer; on the other hand, the high concentration of DMC catalyst will affect the storage stability of the polyether polyol. Therefore, considering the reaction efficiency, polyether quality and polymerization process control, the amount of DMC catalyst should be controlled within a reasonable range under the premise of ensuring the normal polymerization reaction.
[0042] In some optional examples, the mass fraction of the phosphoric acid solution is 80-90wt%, for example, it can be 80wt%, 81wt%, 82wt%, 83wt%, 84wt%, 85wt%, 86wt%, 87wt%, 88wt%, 89wt% or 90wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0043] In some optional examples, before adding propylene oxide and ethylene oxide to the intermediate solution, the temperature in the polymerization reactor is adjusted to 130-140°C, for example, 130°C, 131°C, 132°C, 133°C, 134°C, 135°C, 136°C, 137°C, 138°C, 139°C or 140°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] The process of synthesizing polyether polyols by DMC catalysis is essentially the polymerization reaction of propylene oxide and ethylene oxide. The overly high or low temperature of the polymerization reaction has a great influence on the activity of the DMC catalyst, the polymerization reaction efficiency and the physical and chemical indicators of the polyether polyols finally obtained. The present invention specifically limits that before the polymerization reaction starts, the temperature in the polymerization reactor is adjusted to 130-140°C. When the temperature is lower than 130°C, the activity of the DMC catalyst decreases, the polymerization reaction time becomes longer, and as the catalytic activity of DMC gradually decays, the polymerization reaction may even terminate; when the temperature is higher than 140°C, the catalytic activity of DMC is also greatly enhanced, the instantaneous conversion rate is greatly improved, and it is very easy to cause the occurrence of disproportionation reaction. A small amount of ultra-high molecular weight polyether will be formed during the polymerization reaction, which will lead to the molecular weight distribution of the finally obtained polyether polyol becoming wider, the viscosity increasing, and the optical transparency of the polyether polyol being reduced.
[0045] In some optional examples, before adding propylene oxide and ethylene oxide to the intermediate solution, the pressure in the polymerization reactor is adjusted to 0.18~0.23MPa, for example, it can be 0.18MPa, 0.185MPa, 0.19MPa, 0.195MPa, 0.20MPa, 0.205MPa, 0.21MPa, 0.215MPa, 0.22MPa, 0.225MPa or 0.23MPa, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0046] In some optional examples, the mass ratio of the polyether polyol oligomer, propylene oxide and ethylene oxide when mixed in the intermediate solution is 1:(1.28~1.32):(0.4~0.5), for example, it can be 1:1.28:0.4, 1:1.285:0.41, 1:1.29:0.42, 1:1.295:0.43, 1:1.3:0.44, 1:1.305:0.45, 1:1.31:0.46, 1:1.315:0.47, 1:1.32:0.48, 1:1.3:0.49 or 1:1.31:0.5, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In some optional examples, the polymerization reaction time is 3 to 5 hours, for example, it can be 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0048] In some optional examples, after the polymerization reaction is completed, the polymerization reactor is evacuated until the vacuum degree in the polymerization reactor reaches -0.09~-0.1MPa, and maintained for 1~2h to remove unreacted monomers, and the material is discharged after the temperature in the polymerization reactor drops to 70~80°C; wherein the vacuum degree can be -0.09MPa, -0.091MPa, -0.092MPa, -0.093MPa, -0.094MPa, -0.095MPa, -0.096MPa , -0.097MPa, -0.098MPa, -0.099MPa or -0.1MPa, the holding time can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, and the temperature can be reduced to 70℃, 71℃, 72℃, 73℃, 74℃, 75℃, 76℃, 77℃, 78℃, 79℃ or 80℃, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0049] As a preferred technical solution of the present invention, in step (I), the cyanide complex is prepared by the following method: Anhydrous zinc chloride is dissolved in deionized water to obtain a zinc chloride solution, and a dilute hydrochloric acid solution is added to the zinc chloride solution to obtain a zinc chloride acid solution; tetramethylethylenediamine is added to the zinc chloride acid solution under stirring conditions, and the mixture is mixed to obtain a reaction solution; potassium ferrocyanide solution is added dropwise to the reaction solution, and the mixture is mixed and stirred to react, and after the reaction is completed, the mixture is filtered, washed, and dried to obtain a reaction product; the reaction product is mixed evenly with tert-butyl alcohol, and the mixture is heated under a nitrogen atmosphere to react, and after the reaction is completed, the mixture is filtered, washed, and dried to obtain a white powdery cyanide complex.
[0050] The present invention adopts tetramethylethylenediamine as a chelating agent, uses potassium ferrocyanide and zinc chloride which are cheaper than potassium cobalt cyanide as metal raw materials, and adopts tert-butyl alcohol as an organic ligand to prepare a Zn-Fe cyanide complex. Since the zinc ion has an 18-electron layer structure and has obvious deformability, it is easy to adopt sp 3 d 2 The hybrid orbital forms a complex with the ligand, in which the zinc ion and the two nitrogen atoms of tetramethylethylenediamine, [Fe(CN)6] 3- Two cyano groups and tert-butyloxy oxygen coordinate to form a five-coordinate structure with catalytic ability. Among them, the chelating agent tetramethylethylenediamine can effectively destroy the crystallinity of Zn-Fe cyanide complex molecules. The lower the crystallinity, the higher the catalytic activity of the DMC catalyst. This is because the increase in the non-crystallization of the DMC catalyst can make it easier for propylene oxide and ethylene oxide monomers to penetrate into the coordination structure of the DMC catalyst, promoting its ring-opening polymerization.
[0051] As a preferred technical solution of the present invention, the concentration of anhydrous zinc chloride in the zinc chloride solution is 0.3-0.4 g / mL, for example, it can be 0.3 g / mL, 0.31 g / mL, 0.32 g / mL, 0.33 g / mL, 0.34 g / mL, 0.35 g / mL, 0.36 g / mL, 0.37 g / mL, 0.38 g / mL, 0.39 g / mL or 0.4 g / mL, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0052] In some optional examples, the mixing ratio of anhydrous zinc chloride in the zinc chloride solution and the dilute hydrochloric acid solution is 10g:(0.1~0.5)mL, for example, it can be 10g:0.1mL, 10g:0.15mL, 10g:0.2mL, 10g:0.25mL, 10g:0.3mL, 10g:0.35mL, 10g:0.4mL, 10g:0.45mL or 10g:0.5mL, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0053] In some optional examples, the concentration of the dilute hydrochloric acid solution is 0.1~0.3mol / L, for example, it can be 0.1mol / L, 0.12mol / L, 0.14mol / L, 0.16mol / L, 0.18mol / L, 0.2mol / L, 0.22mol / L, 0.24mol / L, 0.26mol / L, 0.28mol / L or 0.3mol / L, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] In some optional examples, the mass ratio of anhydrous zinc chloride in the zinc chloride acid solution to the tetramethyldiethylamine is 1:(2-3), for example, 1:2.0, 1:2.1, 1:2.2, 1:2.3, 1:2.4, 1:2.5, 1:2.6, 1:2.7, 1:2.8, 1:2.9 or 1:3.0, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] In some optional examples, the mixing time of the zinc chloride acid solution and the tetramethylethylenediamine is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In some optional examples, the mass fraction of the potassium ferrocyanide solution is 8~10wt%, for example, it can be 8.0wt%, 8.2wt%, 8.4wt%, 8.6wt%, 8.8wt%, 9.0wt%, 9.2wt%, 9.4wt%, 9.6wt%, 9.8wt% or 10.0wt%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0057] In some optional examples, the molar ratio of zinc ions in the reaction solution to iron ions in the potassium ferrocyanide solution is (2.8~3.2):1, for example, it can be 2.8:1, 2.85:1, 2.9:1, 2.95:1, 3.0:1, 3.05:1, 3.1:1, 3.15:1 or 3.2:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] In some optional examples, after the potassium ferrocyanide solution is completely added, the formed mixed solution is continued to be stirred for 12 to 24 hours, for example, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] In some optional examples, the mixing ratio of the reaction product and tert-butanol is 1g:(3~5)mL, for example, it can be 1g:3.0mL, 1g:3.2mL, 3.4mL, 1g:3.6mL, 1g:3.8mL, 1g:4.0mL, 1g:4.2mL, 1g:4.4mL, 1g:4.6mL, 1g:4.8mL or 1g:5.0mL, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] In some optional examples, the heating temperature after the reaction product is mixed with tert-butanol is 75-85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0061] In some optional examples, the heating time after the reaction product is mixed with tert-butanol is 40 to 50 hours, for example, it can be 40 hours, 41 hours, 42 hours, 43 hours, 44 hours, 45 hours, 46 hours, 47 hours, 48 hours, 49 hours or 50 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0062] In some optional embodiments, the washing process includes: washing with deionized water for 3 to 5 times, and then washing with tert-butyl alcohol for 3 to 5 times, for example, 3 times, 4 times or 5 times, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0063] In some optional embodiments, the drying temperature is 75-85°C, for example, it can be 75°C, 76°C, 77°C, 78°C, 79°C, 80°C, 81°C, 82°C, 83°C, 84°C or 85°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0064] In some optional embodiments, the drying time is 12 to 24 hours, for example, it can be 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours or 24 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0065] As a preferred technical solution of the present invention, in step (II), the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is 1:(0.93~0.95):(0.4~0.42), for example, it can be 1:0.93:0.4, 1:0.932:0.402, 1:0.934:0.404, 1:0.936:0.406, 1:0.938:0.408, 1:0.94:0.41, 1:0.942:0.412, 1:0.944:0.414, 1:0.946:0.416, 1:0.948:0.418 or 1:0.95:0.42, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0066] The present invention specifically limits the amount of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol to a ratio of 1:(0.93-0.95):(0.4-0.42). When the amount of glutaric acid used exceeds the upper limit of the range defined in the present invention, the optical transparency of the obtained polyester polyol is too low. This is because, on the one hand, the excessive amount of glutaric acid used causes the relative molecular mass of the obtained polyester polyol to become larger, the viscosity to increase, and the transmittance to decrease; on the other hand, since glutaric acid contains impurities such as iron ions, nitrate ions and ash, the color of the polyester polyol will become darker. When glutaric acid is added in excess, it means that the impurities increase, which ultimately leads to an increase in the chromaticity of the polyester polyol and a decrease in transmittance.
[0067] The mechanical properties of the polyurethane elastomer prepared from polyester polyols with high crystallinity are higher, and the optical transparency of the polyurethane elastomer prepared from polyester polyols with low crystallinity is lower. The present invention can change the crystallinity of the obtained polyester polyol by adjusting the ratio of 1,3-propylene glycol and 1,2-propylene glycol. When the ratio of 1,3-propylene glycol and 1,2-propylene glycol is within the numerical range specified in the present invention, a polyurethane elastomer with both mechanical properties and optical transparency can be obtained. The larger the proportion of 1,2-propylene glycol, the lower the crystallization temperature of the obtained polyester polyol. This is because the side chain contained in 1,2-propylene glycol will hinder the formation of hydrogen bonds between polyester polyol molecules, thereby affecting the crystallization properties of polyester polyols. The crystallinity of the generated polyester polyol will decrease, resulting in a decrease in its mechanical properties and an increase in transmittance. However, there is no side chain in the 1,3-propylene glycol molecular chain, and the soft chain segment is relatively long, so it is easier for the molecules to entangle with each other, so that the hydrodynamic volume between the molecules increases, resulting in an increase in the viscosity of the polyester polyol obtained by the reaction, a decrease in transmittance, and an improvement in mechanical properties.
[0068] In some optional examples, the operation process of nitrogen replacement of the esterification reactor includes: 90~100Nm 3 / h flow rate of nitrogen into the esterification reaction kettle until the oxygen content in the esterification reaction kettle is ≤50ppm; wherein the flow rate of nitrogen can be 90Nm 3 / h、91Nm 3 / h、92Nm 3 / h、93Nm 3 / h、94Nm 3 / h、95Nm 3 / h、96Nm 3 / h、97Nm 3 / h、98Nm 3 / h、99Nm 3 / h or 100Nm 3 / h, the oxygen content can be 30ppm, 32ppm, 34ppm, 36ppm, 38ppm, 40ppm, 42ppm, 44ppm, 46ppm, 48ppm or 50ppm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0069] In some optional examples, the operation process of the esterification reaction includes: After the nitrogen replacement of the esterification reaction kettle is completed, the flow rate of nitrogen is lowered, and then the polyester raw material solution is heated to the first esterification temperature at a second heating rate and kept warm for reaction, and then continued to be heated to the second esterification temperature at a third heating rate and kept warm for reaction to carry out the esterification reaction, and the water generated by the reaction is evaporated during the esterification reaction. When the acid value of the reaction product generated by the esterification reaction drops to below 20 mgKOH / g, the reaction product generated by the esterification reaction is sent to a flash evaporator for flash evaporation, and the esterification product is obtained after the flash evaporation is completed.
[0070] During the esterification reaction stage, due to the high concentration of reactants and the overly violent reaction, the steam can easily carry out the small molecule alcohol in the reaction system, resulting in unnecessary waste of raw materials. Therefore, the reaction temperature should be controlled not to be too high at the beginning of the reaction, and a staged heating method should be adopted, first heating to the first esterification temperature, and then continuing to heat to the second esterification temperature.
[0071] In some optional embodiments, after the nitrogen replacement of the esterification reactor is completed, the flow rate of nitrogen is adjusted to 10-20 Nm 3 / h, for example, 10Nm 3 / h、11Nm 3 / h、12Nm 3 / h、13Nm 3 / h、14Nm 3 / h、15Nm 3 / h、16Nm 3 / h、17Nm 3 / h、18Nm 3 / h、19Nm 3 / h or 20Nm 3 / h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0072] In some optional instances, the second heating rate is 8~10℃ / min, for example, it can be 8.0℃ / min, 8.2℃ / min, 8.4℃ / min, 8.6℃ / min, 8.8℃ / min, 9.0℃ / min, 9.2℃ / min, 9.4℃ / min, 9.6℃ / min, 9.8℃ / min or 10.0℃ / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0073] In some optional examples, the first esterification temperature is 150-160°C, for example, it can be 150°C, 151°C, 152°C, 153°C, 154°C, 155°C, 156°C, 157°C, 158°C, 159°C or 160°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0074] In some optional examples, the first esterification temperature is kept warm for 1.5 to 2.5 hours, for example, 1.5 hours, 1.6 hours, 1.7 hours, 1.8 hours, 1.9 hours, 2.0 hours, 2.1 hours, 2.2 hours, 2.3 hours, 2.4 hours or 2.5 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0075] In some optional instances, the third heating rate is 3~5℃ / min, for example, it can be 3.0℃ / min, 3.2℃ / min, 3.4℃ / min, 3.6℃ / min, 3.8℃ / min, 4.0℃ / min, 4.2℃ / min, 4.4℃ / min, 4.6℃ / min, 4.8℃ / min or 5.0℃ / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0076] In some optional examples, the second esterification temperature is 180-190°C, for example, it can be 180°C, 181°C, 182°C, 183°C, 184°C, 185°C, 186°C, 187°C, 188°C, 189°C or 190°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0077] The present invention specifically limits the second esterification temperature to 180-190°C. As the second esterification temperature increases, the molecular weight of the obtained polyester polyol increases first and then decreases, and the esterification rate per unit time increases accordingly, but begins to decrease after increasing to a certain extent. This is because when the second esterification temperature exceeds 190°C, 1,3-propylene glycol and 1,2-propylene glycol will evaporate rapidly, thereby affecting the residence time of 1,3-propylene glycol and 1,2-propylene glycol in the esterification reactor, resulting in incomplete esterification reaction. In addition, too high a temperature will also cause side reactions.
[0078] In some optional examples, the flash evaporation temperature is 230-250°C, for example, it can be 230°C, 232°C, 234°C, 236°C, 238°C, 240°C, 242°C, 244°C, 246°C, 248°C or 250°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0079] In some optional examples, the flash evaporation pressure is 10~20kPa, for example, it can be 10kPa, 11kPa, 12kPa, 13kPa, 14kPa, 15kPa, 16kPa, 17kPa, 18kPa, 19kPa or 20kPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0080] As a preferred technical solution of the present invention, in step (II), the polycondensation reaction process includes: Continuously introducing nitrogen into the polycondensation reaction kettle, transferring the esterification product into the polycondensation reaction kettle, adding the dibutyltin dilaurate into the esterification product, and obtaining a reaction precursor solution; subsequently, stopping introducing nitrogen into the polycondensation reaction kettle, and evacuating the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches a first vacuum degree, after the pressure in the polycondensation reaction kettle is stabilized, heating the reaction precursor solution to a first polycondensation temperature at a fourth heating rate and keeping the temperature for reaction; subsequently, continuing to evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches a second vacuum degree, after the pressure in the polycondensation reaction kettle is stabilized, continuing to heat the reaction precursor solution to a second polycondensation temperature at a fifth heating rate and keeping the temperature for reaction, and obtaining the polyester polyol after the insulation is completed.
[0081] In the present invention, the polycondensation reaction is divided into a pre-polycondensation stage and a polycondensation stage. In the pre-polycondensation stage, there are many small molecules in the reaction system, which makes the reaction system prone to liquid overflow, so it is necessary to introduce nitrogen into the polycondensation reactor to reduce the partial pressure of the reaction system. In the polycondensation stage, due to the high viscosity of the reaction product, the small molecule alcohol and water in the reaction system are not easy to be discharged, which will affect the progress of the polycondensation reaction, so it is necessary to evacuate the polycondensation reactor and place the reaction system under negative pressure to quickly remove the small molecule alcohol in the reaction system and the water generated by the reaction, so as to promote the forward progress of the polycondensation reaction.
[0082] In some optional examples, the flow rate of nitrogen introduced into the polycondensation reactor is 10-20 Nm 3 / h, for example, 10Nm 3 / h、11Nm 3 / h、12Nm 3 / h、13Nm 3 / h、14Nm 3 / h、15Nm 3 / h、16Nm 3 / h、17Nm 3 / h、18Nm 3 / h、19Nm 3 / h or 20Nm 3 / h, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0083] In some optional examples, the added amount of dibutyltin dilaurate is 0.18-0.23% of the mass of the glutaric acid, for example, it can be 0.18%, 0.185%, 0.19%, 0.195%, 0.20%, 0.205%, 0.21%, 0.215%, 0.22%, 0.225% or 0.23%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0084] In some optional instances, the first vacuum degree is -0.02~-0.03MPa, for example, it can be -0.02MPa, -0.021MPa, -0.022MPa, -0.023MPa, -0.024MPa, -0.025MPa, -0.026MPa, -0.027MPa, -0.028MPa, -0.029MPa or -0.03MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0085] In some optional instances, the fourth heating rate is 3~5℃ / min, for example, it can be 3.0℃ / min, 3.2℃ / min, 3.4℃ / min, 3.6℃ / min, 3.8℃ / min, 4.0℃ / min, 4.2℃ / min, 4.4℃ / min, 4.6℃ / min, 4.8℃ / min or 5.0℃ / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0086] In some optional examples, the first polycondensation temperature is 200-210°C, for example, it can be 200°C, 201°C, 202°C, 203°C, 204°C, 205°C, 206°C, 207°C, 208°C, 209°C or 210°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0087] In some optional examples, the reaction is kept at the first condensation temperature for 1 to 2 hours, for example, 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0088] In some optional instances, the second vacuum degree is -0.08~-0.09 MPa, for example, it can be -0.08MPa, -0.081MPa, -0.082MPa, -0.083MPa, -0.084MPa, -0.085MPa, -0.086MPa, -0.087MPa, -0.088MPa, -0.089MPa or -0.09MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0089] In some optional instances, the fifth heating rate is 2~3℃ / min, for example, it can be 2.0℃ / min, 2.1℃ / min, 2.2℃ / min, 2.3℃ / min, 2.4℃ / min, 2.5℃ / min, 2.6℃ / min, 2.7℃ / min, 2.8℃ / min, 2.9℃ / min or 3.0℃ / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0090] In some optional embodiments, the second polycondensation temperature is 230-240°C, for example, it can be 230°C, 231°C, 232°C, 233°C, 234°C, 235°C, 236°C, 237°C, 238°C, 239°C or 240°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0091] The polycondensation temperature is a process condition that has a great influence on the optical transparency of polyester polyols. The present invention specifically limits the second polycondensation temperature to 230-240°C. When the temperature of the second polycondensation reaction is lower than 230°C, it will make it difficult for small molecular by-products and water molecules generated by the reaction to be discharged, resulting in a slowdown in the polycondensation reaction rate; when the temperature of the second polycondensation reaction exceeds 240°C, a series of side reactions such as polyol etherification and alcohol oxidation will occur, generating chromophore by-products with conjugated double bonds, and too high a polycondensation temperature will also cause the carbon chain of the polyester polyol to break or carbonize, thereby deepening the color of the polyester polyol and reducing its transparency.
[0092] In some optional examples, the reaction is kept at the second polycondensation temperature for 3 to 5 hours, for example, 3.0 hours, 3.2 hours, 3.4 hours, 3.6 hours, 3.8 hours, 4.0 hours, 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours or 5.0 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0093] The present invention specifically limits the heat preservation at the second polycondensation temperature to 3 to 5 hours. When the polycondensation reaction time exceeds 5 hours, the polycondensation time is too long and the optical transparency of the obtained polyester polyol decreases. This is because, when the polycondensation reaction is carried out at a high temperature, the reaction system needs to be evacuated and depressurized to remove the small molecular alcohols in the reaction system and the water generated by the reaction, thereby accelerating the reaction rate. This process will inevitably cause a small amount of air to enter the polycondensation reactor, causing the target product to be oxidized, and ultimately affecting the optical transparency of the polyester polyol.
[0094] As a preferred technical solution of the present invention, in step (III), the mass ratio of the polyether polyol to the polyester polyol is (4-5):1, for example, it can be 4.0:1, 4.1:1, 4.2:1, 4.3:1, 4.4:1, 4.5:1, 4.6:1, 4.7:1, 4.8:1, 4.9:1 or 5.0:1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0095] The present invention particularly limits the mass ratio of polyether polyol to polyester polyol to (4-5):1. Within this numerical range, the comprehensive performance of the synthesized polyurethane elastomer is optimal. As the proportion of polyester polyol in the soft segment increases, the tensile strength of the polyurethane elastomer shows an upward trend. This is because the ester group in the polyester polyol has a large polarity and a strong intermolecular force, so that hydrogen bonds can be formed not only between hard segments and hard segments in the synthesized polyurethane elastomer, but also between hard segments and soft segments, which ultimately promotes the improvement of the strength and hardness of the polyurethane elastomer. At the same time, the polyether polyol molecular chain prepared with bisphenol A contains a rigid benzene ring structure, and the polyurethane elastomer synthesized with the polyether polyol as a raw material also gives the polyurethane elastomer higher strength and hardness. However, when the proportion of polyester polyols in the soft segment is too high, the proportion of polyether polyols is relatively too low, and the degree of cross-linking with the isocyanate functional group decreases; in addition, the bond energy of the ether group is smaller than that of the ester group, and the number of ether groups in the polyurethane elastomer molecular chain is too small, resulting in a decrease in the flexibility of the soft segment molecular chain, and ultimately causing the elongation at break of the polyurethane elastomer to decrease.
[0096] In some optional examples, the vacuum degree of the polyether polyol and the polyester polyol during dehydration is -0.09 to -0.095 MPa, for example, it can be -0.09 MPa, -0.0905 MPa, -0.091 MPa, -0.0915 MPa, -0.092 MPa, -0.0925 MPa, -0.093 MPa, -0.0935 MPa, -0.094 MPa, -0.0945 MPa or -0.095 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0097] In some optional examples, the heating temperature of the polyether polyol and polyester polyol during dehydration is 100-110°C, for example, it can be 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0098] In some optional examples, the dehydration time of the polyether polyol and the polyester polyol is 1 to 2 hours, for example, it can be 1.0h, 1.1h, 1.2h, 1.3h, 1.4h, 1.5h, 1.6h, 1.7h, 1.8h, 1.9h or 2.0h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0099] In some optional examples, the moisture content of the polyether polyol and polyester polyol after dehydration is ≤0.05%, for example, it can be 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045% or 0.05%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0100] In some optional examples, the vacuum degree of the 1,4-butanediol during dehydration is -0.09 to -0.095 MPa, for example, it can be -0.09 MPa, -0.0905 MPa, -0.091 MPa, -0.0915 MPa, -0.092 MPa, -0.0925 MPa, -0.093 MPa, -0.0935 MPa, -0.094 MPa, -0.0945 MPa or -0.095 MPa, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0101] In some optional examples, the heating temperature of the 1,4-butanediol during dehydration is 100-110°C, for example, it can be 100°C, 101°C, 102°C, 103°C, 104°C, 105°C, 106°C, 107°C, 108°C, 109°C or 110°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0102] In some optional examples, the dehydration time of the 1,4-butanediol is 1 to 2 hours, for example, it can be 1.0 h, 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2.0 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0103] In some optional examples, the water content of the 1,4-butanediol after dehydration is ≤0.05%, for example, it can be 0.01%, 0.015%, 0.02%, 0.025%, 0.03%, 0.035%, 0.04%, 0.045% or 0.05%, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0104] In some optional examples, the mass ratio of the 1,4-butanediol to the tertiary amine catalyst is 1:(0.03~0.05), for example, it can be 1:0.03, 1:0.032, 1:0.034, 1:0.036, 1:0.038, 1:0.04, 1:0.042, 1:0.044, 1:0.046, 1:0.048 or 1:0.05, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0105] In some optional examples, the tertiary amine catalyst includes any one of pentamethyldiethylenetriamine, N,N-dimethylcyclohexylamine, triethylenediamine, triethylamine or bis(dimethylamino)ethyl ether, or a combination of at least two thereof.
[0106] In some optional examples, the aliphatic isocyanate includes hexamethylene diisocyanate and / or isophorone diisocyanate.
[0107] As a preferred technical solution of the present invention, in step (III), before the A component, the B component and the C component are mixed, the temperature of the A component and the C component is controlled at 80-90°C, for example, 80°C, 81°C, 82°C, 83°C, 84°C, 85°C, 86°C, 87°C, 88°C, 89°C or 90°C; the temperature of the B component is controlled at 40-50°C, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0108] In some optional examples, the mass ratio of the A component, the B component and the C component when mixed is 1:(0.2~0.3):(0.05~0.1), for example, it can be 1:0.2:0.05, 1:0.21:0.055, 1:0.22:0.06, 1:0.23:0.065, 1:0.24:0.07, 1:0.25:0.075, 1:0.26:0.08, 1:0.27:0.085, 1:0.28:0.09, 1:0.29:0.095 or 1:0.3:0.1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0109] The present invention particularly limits the mass ratio of component A, component B and component C when mixed to 1:(0.2-0.3):(0.05-0.1). As the amount of component A increases, the tensile strength and hardness of the finally synthesized polyurethane elastomer gradually decrease. This is because the increase in the amount of component A means that the content of the soft segment in the synthesized polyurethane elastomer increases, while the content of the hard segment decreases, which is not conducive to the formation of hydrogen bonds between the hard segments, and the degree of microphase separation decreases, thereby resulting in reduced strength and hardness of the polyurethane elastomer.
[0110] As the amount of component B increases, the tensile strength and hardness of the final synthesized polyurethane elastomer gradually increase. This is because as the amount of component B increases, the content of hard segments in the synthesized polyurethane elastomer increases, and the hydrogen bonding force between molecules increases. Therefore, the strength and hardness of the polyurethane elastomer increase accordingly.
[0111] In some optional instances, the temperature of the mold is 90-100°C, for example, it can be 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C or 100°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0112] In some optional examples, the vulcanization temperature is 85-95°C, for example, it can be 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C or 95°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0113] In some optional examples, the vulcanization time is 12 to 14 hours, for example, it can be 12 hours, 12.2 hours, 12.4 hours, 12.6 hours, 12.8 hours, 13 hours, 13.2 hours, 13.4 hours, 13.6 hours, 13.8 hours or 14 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0114] In a second aspect, the present invention provides a transparent grade thermoplastic polyurethane elastomer prepared by the method for preparing a transparent grade thermoplastic polyurethane elastomer described in the first aspect.
[0115] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses a compound of polyether polyol and polyester polyol as a two-component soft segment, and uses aliphatic isocyanate and 1,4-butanediol as a hard segment. The preparation process of polyether polyol and polyester polyol is optimized and adjusted, and the compatibility of the two is improved by changing the ratio and structure of the two, so as to give full play to the performance advantages of the two, and synthesize a thermoplastic polyurethane elastomer with both mechanical properties and optical transparency. BRIEF DESCRIPTION OF THE DRAWINGS
[0116] Figure 1 A flow chart of a method for preparing a transparent grade thermoplastic polyurethane elastomer provided in Examples 1 to 5 of the present invention; Figure 2 This is the infrared spectrum of the cyanide complex prepared in Example 1 of the present invention; Figure 3 The XRD spectra of the cyanide complexes prepared in Example 1 and Comparative Example 11 of the present invention; Figure 4 This is a scanning electron microscope image of the cyanide complex prepared in Example 1 of the present invention; Figure 5 This is a scanning electron microscope image of the cyanide complex prepared in Comparative Example 11 of the present invention; Figure 6 This is an infrared spectrum of the polyether polyol prepared in Example 1 of the present invention; Figure 7 This is the infrared spectrum of the polyester polyol prepared in Example 1 of the present invention; Figure 8 This is an infrared spectrum of the thermoplastic polyurethane elastomer prepared in Example 1 of the present invention; Fig. 9 This is a physical picture of the thermoplastic polyurethane elastomer prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0117] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and their accompanying drawings. The embodiments recorded herein are specific embodiments of the present invention, which are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limitations on the embodiments of the present invention and the scope of protection of the present invention. In addition to the embodiments recorded herein, those skilled in the art can also adopt other obvious technical solutions based on the contents disclosed in the claims of this application and its specification, including technical solutions that adopt any obvious replacements and modifications to the embodiments recorded herein.
[0118] The chemical reagents used in this specific embodiment are all commercially available products, and their specifications, models, manufacturers and other information are as follows: Anhydrous zinc chloride: purity 99%, purchased from Wuhan Jiyesheng Chemical Co., Ltd.; Tetramethylethylenediamine: purity 99.5%, purchased from Shandong Jiuan Chemical Co., Ltd.; Potassium ferrocyanide: S24282-500g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Tert-butyl alcohol: purity 99.5%, M25553, purchased from Shanghai Myrrel Biochemical Technology Co., Ltd.; Castor oil: S24344-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Bisphenol A: S30294-100 g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Potassium hydroxide: purity 90%, purchased from Shandong Jinshengrun Chemical Co., Ltd.; Propylene oxide: purity 99%, purchased from Shandong Yihong Chemical Co., Ltd.; Phosphoric acid: purity 99%, purchased from Jinan Jumeihui Chemical Co., Ltd.; Ethylene oxide: purity 99%, purchased from Shanghai Myril Biochemical Technology Co., Ltd.; Glutaric acid: S30139-100g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; 1,3-Propanediol: S24136-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; 1,2-Propanediol: purity 99%, purchased from Shandong Yihong Chemical Co., Ltd.; Dibutyltin dilaurate: industrial grade, purchased from Jinan Century Tongda Chemical Co., Ltd.; Aliphatic isocyanate: purity 99.5%, purchased from Shanghai Fuzhe Chemical Co., Ltd.; 1,4-Butanediol: S24138-500ml, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Pentamethyldiethylenetriamine: purity 99%, purchased from Dongguan Guangsiyuan Polyurethane Materials Co., Ltd.; N, N-dimethylcyclohexylamine: purity 99%, purchased from Shandong Mantanghong New Materials Co., Ltd.; Triethylenediamine: S24250-250g, purchased from Shanghai Yuanye Biotechnology Co., Ltd.; Triethylamine: purity 99%, purchased from Jinan Jumeihui Chemical Co., Ltd.; Bis(dimethylamino)ethyl ether: purity 99%, purchased from Guangzhou Shanghe Chemical Technology Co., Ltd.; Hexamethylene diisocyanate: purity 99.5%, purchased from Shanghai Fuzhe Chemical Co., Ltd.; Isophorone diisocyanate: purity 99%, purchased from Wuhan Jixinyibang Biotechnology Co., Ltd.
[0119] Example 1 This embodiment provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, such as Figure 1 As shown, the preparation method comprises: Step (1), dissolving anhydrous zinc chloride with a concentration of 0.3 g / mL in deionized water to obtain a zinc chloride solution, adding a dilute hydrochloric acid solution with a concentration of 0.1 mol / L to the zinc chloride solution, wherein the mixing ratio of anhydrous zinc chloride to the dilute hydrochloric acid solution in the zinc chloride solution is 10 g:0.1 mL, and mixing well to obtain a zinc chloride acid solution; Tetramethylethylenediamine was added to the zinc chloride acid solution under stirring, the mass ratio of anhydrous zinc chloride in the zinc chloride acid solution to tetramethyldiethylamine was 1:2, and the mixture was mixed for 12 hours to obtain a reaction solution; a potassium ferrocyanide solution with a mass fraction of 8wt% was added dropwise to the reaction solution, the molar ratio of zinc ions in the reaction solution to iron ions in the potassium ferrocyanide solution was 2.8:1, and after the potassium ferrocyanide solution was completely added dropwise, the formed mixed solution was stirred for 12 hours to react, and after the reaction was completed, the solution was filtered, and then the solid product obtained by filtration was washed 3 times with deionized water, and then washed 3 times with tert-butyl alcohol, and after the washing was completed, it was placed under vacuum drying at 75°C for 24 hours to obtain a reaction product; The reaction product was mixed evenly with tert-butanol in a mixing ratio of 1 g:3 mL, and heated at 75° C. for 50 h in a nitrogen atmosphere to react. After the reaction was completed, the solid product was filtered, and then washed 3 times with deionized water and 3 times with tert-butanol. After washing, the solid product was dried under vacuum at 75° C. for 24 h to obtain a white powdery cyanide complex. Step (2), castor oil, bisphenol A and potassium hydroxide are mixed uniformly in a mass ratio of 100:50:1.2 to obtain a polyether raw material solution, and the polyether raw material solution is added to a polymerization reactor at 90 Nm 3 / h flow rate of nitrogen into the polymerization reactor until the oxygen content in the polymerization reactor reaches 50ppm, completing nitrogen replacement; then the polyether raw material solution is heated to 100°C, and 60Nm 3 Nitrogen was bubbled in at a flow rate of / h, and at the same time, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.09MPa and maintained for 2h, completing nitrogen bubbling decompression dehydration, and the water content of the polyether raw material solution after dehydration was 0.12%; Subsequently, the temperature in the polymerization reactor was adjusted to 90° C., and the pressure was adjusted to 0.23 MPa, and propylene oxide was added to the polyether raw material solution, and the ratio of the total mass of castor oil and bisphenol A in the polyether raw material solution to the mass of propylene oxide was 8:1. The mixture was stirred and heated at 90° C. and 0.23 MPa for 1 hour, and then heated to 120° C. at a heating rate of 1° C. / min and kept warm for 3 hours. When the pressure in the polymerization reactor continued to decrease and dropped to negative pressure, and the temperature began to continue to rise, it indicated that the induction reaction was completed, and a polyether polyol oligomer was obtained; Adding the cyanide complex and phosphoric acid solution prepared in step (1) to the polyether polyol oligomer, wherein the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is 1000:0.1:0.008, and the mass fraction of the phosphoric acid solution is 80wt%, and mixing them uniformly to obtain an intermediate solution; The temperature in the polymerization reactor was adjusted to 130° C., and the pressure was adjusted to 0.23 MPa. Propylene oxide and ethylene oxide were added to the intermediate solution. The mass ratio of the polyether polyol oligomer, propylene oxide and ethylene oxide in the intermediate solution was 1:1.28:0.4 when mixed. The polymerization reaction was carried out under stirring and heating at 130° C. and 0.23 MPa for 5 h. After the polymerization reaction was completed, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.09 MPa and maintained for 2 h to remove unreacted monomers. The material was discharged after the temperature in the polymerization reactor dropped to 70° C. to obtain a polyether polyol. Step (3), glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol are mixed uniformly to obtain a polyester raw material solution, wherein the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is 1:0.93:0.4; the polyester raw material solution is added to an esterification reaction kettle and heated at 90 Nm 3 Nitrogen was introduced into the esterification reaction kettle at a flow rate of / h until the oxygen content in the esterification reaction kettle reached 50ppm, thus completing the nitrogen replacement; After nitrogen replacement is completed, adjust the nitrogen flow rate to 10Nm 3 / h, then heating the polyester raw material solution to 150°C at a heating rate of 8°C / min and keeping the temperature for reaction for 2.5h, then continuing to heat to 180°C at a heating rate of 3°C / min and keeping the temperature for esterification reaction, distilling the water generated by the reaction during the esterification reaction, and when the acid value of the reaction product generated by the esterification reaction drops below 20mgKOH / g, sending the reaction product generated by the esterification reaction into a flash evaporator for flash evaporation, the flash evaporation temperature is 230°C, the flash evaporation pressure is 20kPa, and the esterification product is obtained after the flash evaporation; Then, at 10Nm 3 / h flow rate into the polycondensation reaction kettle, transfer the esterification product to the polycondensation reaction kettle, add dibutyltin dilaurate to the esterification product, the amount of dibutyltin dilaurate added is 0.18% of the mass of glutaric acid, and mix well to obtain a reaction precursor solution; then, stop passing nitrogen into the polycondensation reaction kettle, and evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches -0.02MPa, after the pressure in the polycondensation reaction kettle is stable, heat the reaction precursor solution to 200°C at a heating rate of 3°C / min and keep it warm for reaction for 2h; then, continue to evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches -0.08MPa, after the pressure in the polycondensation reaction kettle is stable, continue to heat the reaction precursor solution to 230°C at a heating rate of 2°C / min and keep it warm for reaction for 5h, and obtain polyester polyol after the insulation is completed; Step (4), the polyether polyol prepared in step (2) and the polyester polyol prepared in step (3) are mixed uniformly in a mass ratio of 4:1, and dehydrated at -0.09 MPa and 100°C for 2 hours to obtain component A with a water content of 0.03%; hexamethylene diisocyanate is used as component B; 1,4-butanediol is dehydrated at -0.09 MPa and 100°C for 2 hours to obtain 1,4-butanediol with a water content of 0.03%, and the dehydrated 1,4-butanediol and pentamethyldiethylenetriamine are mixed uniformly in a mass ratio of 1:0.03 to obtain component C; Component A at 80°C, component B at 40°C and component C at 80°C are mixed evenly in a mass ratio of 1:0.2:0.05 and injected into a mold at 90°C. The mixture is demolded after cooling and finally heated for vulcanization at a temperature of 85°C and a vulcanization time of 14 hours. After the vulcanization is completed, the transparent grade thermoplastic polyurethane elastomer is obtained.
[0120] Figure 2 The infrared spectrum of the cyanide complex prepared in this example is shown in the figure. -1 and 2100cm -1 The stretching vibration absorption peak of -CN and Fe-CN in the Fe-CN-Zn structure is 1610 cm -1 The C=N stretching vibration absorption peak in the Fe-CN-Zn structure is 3590cm -1 The peaks are the stretching vibration absorption peaks of hydroxyl groups. The existence of these characteristic peaks indicates that the synthesized product is a Zn-Fe cyanide complex.
[0121] Figure 6 This is the infrared spectrum of the polyether polyol prepared in this example. It can be seen from the figure that 3480cm -1 The stretching vibration absorption peak of -OH is 2980cm -1The antisymmetric stretching vibration absorption peak of -CH3 is 1608cm -1 、1510cm -1 and 1453cm -1 The peak at 1090 cm is the stretching vibration absorption peak of the carbon-carbon double bond in the benzene ring. -1 The peaks at the bottom are the stretching vibration absorption peaks of the ether group. The existence of these characteristic peaks indicates that the synthesized product is a polyether polyol.
[0122] Figure 7 This is the infrared spectrum of the polyester polyol prepared in this example. It can be seen from the figure that 2934cm -1 The stretching vibration absorption peak of -CH2 is 1340cm -1 The -CH2 bending vibration absorption peak is 1716cm -1 The stretching vibration absorption peak of the carbonyl group in the ester bond is 1151 cm -1 and 1028cm -1 The presence of these characteristic peaks indicates that the synthesized product is polyester polyol.
[0123] Figure 8 The infrared spectrum of the thermoplastic polyurethane elastomer prepared in this example is shown in the figure. It can be seen that at 3500cm -1 ~3390cm -1 The stretching vibration absorption peak of -OH and -NH is 2275cm -1 The asymmetric stretching vibration absorption peak of the -NCO functional group is 2920cm -1 The stretching vibration absorption peaks of methyl and methylene are at 1219 cm -1 The CO stretching vibration absorption peak of polyester is 1067 cm -1 The irregular stretching vibration absorption peak of the COC bond is shown at .
[0124] Fig. 9 This is a physical picture of the thermoplastic polyurethane elastomer prepared in this example. It can be seen from the figure that the thermoplastic polyurethane elastomer prepared in the present invention has excellent optical transparency.
[0125] Example 2 This embodiment provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, such as Figure 1 As shown, the preparation method comprises: Step (1), dissolving anhydrous zinc chloride with a concentration of 0.32 g / mL in deionized water to obtain a zinc chloride solution, adding a dilute hydrochloric acid solution with a concentration of 0.15 mol / L to the zinc chloride solution, wherein the mixing ratio of the anhydrous zinc chloride in the zinc chloride solution to the dilute hydrochloric acid solution is 10 g:0.2 mL, and mixing well to obtain a zinc chloride acid solution; Tetramethylethylenediamine was added to the zinc chloride acid solution under stirring, the mass ratio of anhydrous zinc chloride to tetramethyldiethylamine in the zinc chloride acid solution was 1:2.2, and the mixture was mixed for 15 hours to obtain a reaction solution; a potassium ferrocyanide solution with a mass fraction of 8.5wt% was added dropwise to the reaction solution, the molar ratio of zinc ions in the reaction solution to iron ions in the potassium ferrocyanide solution was 2.9:1, and after the potassium ferrocyanide solution was completely added dropwise, the formed mixed solution was stirred for 15 hours to react, and after the reaction was completed, the solution was filtered, and the solid product obtained by filtration was subsequently washed 3 times with deionized water, and then washed 3 times with tert-butyl alcohol, and after the washing was completed, the solution was placed under vacuum drying at 78°C for 21 hours to obtain a reaction product; The reaction product was mixed evenly with tert-butanol in a mixing ratio of 1 g:3.5 mL, and heated under a nitrogen atmosphere and 78° C. for 48 h to react. After the reaction was completed, the solid product was filtered, and then washed 3 times with deionized water and 3 times with tert-butanol. After washing, the solid product was placed in a vacuum dryer at 78° C. for 21 h to obtain a white powdery cyanide complex. Step (2), castor oil, bisphenol A and potassium hydroxide are mixed uniformly in a mass ratio of 100:52:1.3 to obtain a polyether raw material solution, and the polyether raw material solution is added to a polymerization reactor at 92Nm 3 Nitrogen was introduced into the polymerization reactor at a flow rate of 65 Nm / h until the oxygen content in the polymerization reactor reached 48 ppm, thus completing nitrogen replacement. The polyether raw material solution was then heated to 102°C, and nitrogen was introduced into the polyether raw material solution from the bottom of the polymerization reactor at a flow rate of 65 Nm / h. 3 Nitrogen was bubbled in at a flow rate of / h, and at the same time, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.092MPa and maintained for 1.8h, completing nitrogen bubbling decompression dehydration, and the water content of the polyether raw material solution after dehydration was 0.13%; Subsequently, the temperature in the polymerization reactor was adjusted to 92° C., and the pressure was adjusted to 0.22 MPa, and propylene oxide was added to the polyether raw material solution, and the mass ratio of castor oil and bisphenol A in the polyether raw material solution to propylene oxide was 8.5:1. The mixture was stirred and heated for 0.8 h under the reaction conditions of 92° C. and 0.22 MPa, and then heated to 122° C. at a heating rate of 1.5° C. / min and kept warm for 2.8 h. When the pressure in the polymerization reactor continued to decrease and dropped to negative pressure, and the temperature began to continue to rise, it indicated that the induction reaction was completed, and a polyether polyol oligomer was obtained; Adding the cyanide complex and phosphoric acid solution prepared in step (1) to the polyether polyol oligomer, wherein the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is 1000:0.105:0.0082, and the mass fraction of the phosphoric acid solution is 82wt%, and mixing them uniformly to obtain an intermediate solution; The temperature in the polymerization reactor was adjusted to 132° C., and the pressure was adjusted to 0.22 MPa. Propylene oxide and ethylene oxide were added to the intermediate solution. The mass ratio of the polyether polyol oligomer, propylene oxide and ethylene oxide in the intermediate solution was 1:1.29:0.42 when mixed. The polymerization reaction was carried out by stirring and heating for 4.5 hours under the reaction conditions of 132° C. and 0.22 MPa. After the polymerization reaction was completed, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.092 MPa and maintained for 1.8 hours to remove unreacted monomers. The material was discharged after the temperature in the polymerization reactor dropped to 72° C. to obtain a polyether polyol. Step (3), glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol are mixed uniformly to obtain a polyester raw material solution, wherein the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is 1:0.935:0.405; the polyester raw material solution is added to an esterification reaction kettle, and heated at 92 Nm 3 Nitrogen was introduced into the esterification reaction kettle at a flow rate of / h until the oxygen content in the esterification reaction kettle reached 48ppm, thus completing the nitrogen replacement; After nitrogen replacement is completed, adjust the nitrogen flow rate to 12Nm 3 / h, then heating the polyester raw material solution to 152°C at a heating rate of 8.5°C / min and keeping the temperature for reaction for 2.2h, then continuing to heat to 182°C at a heating rate of 3.5°C / min and keeping the temperature for esterification reaction, distilling the water generated by the reaction during the esterification reaction, and when the acid value of the reaction product generated by the esterification reaction drops below 20mgKOH / g, sending the reaction product generated by the esterification reaction into a flash evaporator for flash evaporation, the flash evaporation temperature is 235°C, the flash evaporation pressure is 18kPa, and the esterification product is obtained after the flash evaporation; Then, with 12Nm 3 / h flow rate into the polycondensation reaction kettle, the esterification product is transferred to the polycondensation reaction kettle, dibutyltin dilaurate is added to the esterification product, the amount of dibutyltin dilaurate added is 0.19% of the mass of glutaric acid, and the reaction precursor solution is obtained after uniform mixing; then, the nitrogen is stopped from being introduced into the polycondensation reaction kettle, and the polycondensation reaction kettle is evacuated until the pressure in the polycondensation reaction kettle reaches -0.022MPa, after the pressure in the polycondensation reaction kettle is stabilized, the reaction precursor solution is heated to 202°C at a heating rate of 3.5°C / min and kept warm for reaction for 1.8h; then, the polycondensation reaction kettle is continued to be evacuated until the pressure in the polycondensation reaction kettle reaches -0.082MPa, after the pressure in the polycondensation reaction kettle is stabilized, the reaction precursor solution is continued to be heated to 232°C at a heating rate of 2.2°C / min and kept warm for reaction for 4.5h, and polyester polyol is obtained after the insulation is completed; Step (4), the polyether polyol prepared in step (2) and the polyester polyol prepared in step (3) are mixed uniformly at a mass ratio of 4.2:1, and dehydrated at -0.091 MPa and 102° C. for 1.8 h to obtain component A with a water content of 0.03%; hexamethylene diisocyanate is used as component B; 1,4-butanediol is dehydrated at -0.091 MPa and 102° C. for 1.8 h to obtain 1,4-butanediol with a water content of 0.03%, and the dehydrated 1,4-butanediol and N,N-dimethylcyclohexylamine are mixed uniformly at a mass ratio of 1:0.035 to obtain component C; Component A at 82°C, component B at 42°C and component C at 82°C are mixed evenly in a mass ratio of 1:0.22:0.06 and injected into a mold at 92°C. The mixture is demolded after cooling and finally heated for vulcanization at a temperature of 88°C and a time of 13.5 hours. After the vulcanization is completed, the transparent grade thermoplastic polyurethane elastomer is obtained.
[0126] Example 3 This embodiment provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, such as Figure 1 As shown, the preparation method comprises: Step (1), dissolving anhydrous zinc chloride with a concentration of 0.35 g / mL in deionized water to obtain a zinc chloride solution, adding a dilute hydrochloric acid solution with a concentration of 0.2 mol / L to the zinc chloride solution, wherein the mixing ratio of anhydrous zinc chloride to the dilute hydrochloric acid solution in the zinc chloride solution is 10 g:0.3 mL, and mixing well to obtain a zinc chloride acid solution; Tetramethylethylenediamine was added to the zinc chloride acid solution under stirring, the mass ratio of anhydrous zinc chloride in the zinc chloride acid solution to tetramethyldiethylamine was 1:2.5, and the mixture was mixed for 18 hours to obtain a reaction solution; a potassium ferrocyanide solution with a mass fraction of 9wt% was added dropwise to the reaction solution, the molar ratio of zinc ions in the reaction solution to iron ions in the potassium ferrocyanide solution was 3:1, and after the potassium ferrocyanide solution was completely added dropwise, the formed mixed solution was stirred for 18 hours to react, and after the reaction was completed, the solution was filtered, and then the solid product obtained by filtration was washed 4 times with deionized water, and then washed 4 times with tert-butyl alcohol, and after the washing was completed, it was placed in a vacuum dryer at 80°C for 18 hours to obtain a reaction product; The reaction product and tert-butanol were mixed evenly in a mixing ratio of 1 g:4 mL, and heated under a nitrogen atmosphere and 80° C. for 45 h to react. After the reaction was completed, the solid product was filtered, and then washed 4 times with deionized water and 4 times with tert-butanol. After washing, the solid product was placed in a vacuum dryer at 80° C. for 18 h to obtain a white powdery cyanide complex. Step (2), castor oil, bisphenol A and potassium hydroxide are mixed uniformly in a mass ratio of 100:55:1.4 to obtain a polyether raw material solution, and the polyether raw material solution is added to a polymerization reactor at 95Nm 3 Nitrogen was introduced into the polymerization reactor at a flow rate of 70 Nm / h until the oxygen content in the polymerization reactor reached 45 ppm, thus completing nitrogen replacement. The polyether raw material solution was then heated to 105°C, and nitrogen was introduced into the polyether raw material solution from the bottom of the polymerization reactor at a flow rate of 70 Nm / h. 3 / h flow rate of nitrogen, at the same time, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.095MPa and maintained for 1.5h, to complete nitrogen bubbling decompression dehydration, the water content of the polyether raw material solution after dehydration was 0.13%; Subsequently, the temperature in the polymerization reactor was adjusted to 95° C., and the pressure was adjusted to 0.2 MPa, and propylene oxide was added to the polyether raw material solution, and the total mass ratio of castor oil and bisphenol A in the polyether raw material solution to the mass ratio of propylene oxide was 9:1. The mixture was stirred and heated for 0.7 h under the reaction conditions of 95° C. and 0.2 MPa, and then heated to 125° C. at a heating rate of 2° C. / min and kept for reaction for 2.5 h. When the pressure in the polymerization reactor continued to decrease and dropped to negative pressure, and the temperature began to continue to rise, it indicated that the induction reaction was completed, and a polyether polyol oligomer was obtained; Adding the cyanide complex and phosphoric acid solution prepared in step (1) to the polyether polyol oligomer, wherein the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is 1000:0.11:0.0085, and the mass fraction of the phosphoric acid solution is 85wt%, and mixing them uniformly to obtain an intermediate solution; The temperature in the polymerization reactor was adjusted to 135° C., and the pressure was adjusted to 0.2 MPa. Propylene oxide and ethylene oxide were added to the intermediate solution. The mass ratio of the polyether polyol oligomer, propylene oxide and ethylene oxide in the intermediate solution was 1:1.3:0.45 when mixed. The polymerization reaction was carried out by stirring and heating for 4 hours under the reaction conditions of 135° C. and 0.2 MPa. After the polymerization reaction was completed, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.095 MPa and maintained for 1.5 hours to remove unreacted monomers. The material was discharged after the temperature in the polymerization reactor dropped to 75° C. to obtain a polyether polyol. Step (3), glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol are mixed uniformly to obtain a polyester raw material solution, wherein the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is 1:0.94:0.41; the polyester raw material solution is added to an esterification reaction kettle and heated at 95 Nm 3 Nitrogen was introduced into the esterification reaction kettle at a flow rate of / h until the oxygen content in the esterification reaction kettle reached 45ppm, thus completing the nitrogen replacement; After nitrogen replacement is completed, adjust the nitrogen flow rate to 15Nm 3 / h, then heating the polyester raw material solution to 155°C at a heating rate of 9°C / min and keeping the temperature for reaction for 2h, then continuing to heat to 185°C at a heating rate of 4°C / min and keeping the temperature for esterification reaction, distilling the water generated by the reaction during the esterification reaction, and when the acid value of the reaction product generated by the esterification reaction drops below 20mgKOH / g, sending the reaction product generated by the esterification reaction into a flash evaporator for flash evaporation, the flash evaporation temperature is 240°C, the flash evaporation pressure is 15kPa, and the esterification product is obtained after the flash evaporation; Then, at 15Nm 3 / h flow rate into the polycondensation reaction kettle, transfer the esterification product to the polycondensation reaction kettle, add dibutyltin dilaurate to the esterification product, the amount of dibutyltin dilaurate added is 0.2% of the mass of glutaric acid, and mix well to obtain a reaction precursor solution; then, stop passing nitrogen into the polycondensation reaction kettle, and evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches -0.025MPa, after the pressure in the polycondensation reaction kettle is stable, heat the reaction precursor solution to 205°C at a heating rate of 4°C / min and keep it warm for reaction for 1.5h; then, continue to evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches -0.085MPa, after the pressure in the polycondensation reaction kettle is stable, continue to heat the reaction precursor solution to 235°C at a heating rate of 2.5°C / min and keep it warm for reaction for 4h, and after the insulation is completed, obtain polyester polyol; Step (4), the polyether polyol prepared in step (2) and the polyester polyol prepared in step (3) are mixed uniformly at a mass ratio of 4.5:1, and dehydrated at -0.092 MPa and 105°C for 1.5 hours to obtain component A with a water content of 0.04%; hexamethylene diisocyanate is used as component B; 1,4-butanediol is dehydrated at -0.092 MPa and 105°C for 1.5 hours to obtain 1,4-butanediol with a water content of 0.04%, and the dehydrated 1,4-butanediol and triethylenediamine are mixed uniformly at a mass ratio of 1:0.04 to obtain component C; Component A at 85°C, component B at 45°C and component C at 85°C are mixed evenly in a mass ratio of 1:0.25:0.07 and injected into a mold at 95°C. The mixture is demolded after cooling and finally heated for vulcanization at a temperature of 90°C and a vulcanization time of 13 hours. After the vulcanization, the transparent grade thermoplastic polyurethane elastomer is obtained.
[0127] Example 4 This embodiment provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, such as Figure 1 As shown, the preparation method comprises: Step (1), dissolving anhydrous zinc chloride with a concentration of 0.38 g / mL in deionized water to obtain a zinc chloride solution, adding a dilute hydrochloric acid solution with a concentration of 0.25 mol / L to the zinc chloride solution, wherein the mixing ratio of anhydrous zinc chloride to the dilute hydrochloric acid solution in the zinc chloride solution is 10 g:0.4 mL, and mixing well to obtain a zinc chloride acid solution; Tetramethylethylenediamine was added to the zinc chloride acid solution under stirring, the mass ratio of anhydrous zinc chloride in the zinc chloride acid solution to tetramethyldiethylamine was 1:2.8, and the mixture was mixed for 21 hours to obtain a reaction solution; a potassium ferrocyanide solution with a mass fraction of 9.5wt% was added dropwise to the reaction solution, the molar ratio of zinc ions in the reaction solution to iron ions in the potassium ferrocyanide solution was 3.1:1, and after the potassium ferrocyanide solution was completely added dropwise, the formed mixed solution was stirred for 21 hours to react, and after the reaction was completed, the solution was filtered, and the solid product obtained by filtration was subsequently washed 5 times with deionized water, and then washed 5 times with tert-butyl alcohol, and after the washing was completed, the solid product was placed under vacuum drying at 82°C for 15 hours to obtain a reaction product; The reaction product was mixed evenly with tert-butanol in a mixing ratio of 1 g:4.5 mL, and heated under a nitrogen atmosphere and 82° C. for 42 h to react. After the reaction was completed, the solid product was filtered, and then washed 5 times with deionized water and then washed 5 times with tert-butanol. After washing, it was placed in a vacuum dryer at 82° C. for 15 h to obtain a white powdery cyanide complex. Step (2), castor oil, bisphenol A and potassium hydroxide are mixed uniformly in a mass ratio of 100:58:1.4 to obtain a polyether raw material solution, and the polyether raw material solution is added to a polymerization reactor at 98Nm 3 Nitrogen was introduced into the polymerization reactor at a flow rate of 75 Nm / h until the oxygen content in the polymerization reactor reached 42 ppm, completing nitrogen replacement. The polyether raw material solution was then heated to 108°C, and nitrogen was introduced into the polyether raw material solution from the bottom of the polymerization reactor at a flow rate of 75 Nm / h. 3 / h flow rate of nitrogen, at the same time, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.098MPa and maintained for 1.2h, to complete nitrogen bubbling decompression dehydration, the water content of the polyether raw material solution after dehydration was 0.14%; Subsequently, the temperature in the polymerization reactor was adjusted to 98° C., and the pressure was adjusted to 0.19 MPa, and propylene oxide was added to the polyether raw material solution, and the mass ratio of castor oil and bisphenol A in the polyether raw material solution to propylene oxide was 9.5:1. The mixture was stirred and heated for 0.6 h under the reaction conditions of 98° C. and 0.19 MPa, and then heated to 128° C. at a heating rate of 2.5° C. / min and kept for reaction for 2.2 h. When the pressure in the polymerization reactor continued to decrease and dropped to negative pressure, and the temperature began to continue to rise, it indicated that the induction reaction was completed, and a polyether polyol oligomer was obtained; Add the cyanide complex and phosphoric acid solution prepared in step (1) to the polyether polyol oligomer, wherein the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is 1000:0.115:0.0088, and the mass fraction of the phosphoric acid solution is 88wt%, and mix well to obtain an intermediate solution; The temperature in the polymerization reactor was adjusted to 138° C., and the pressure was adjusted to 0.19 MPa. Propylene oxide and ethylene oxide were added to the intermediate solution. The mass ratio of the polyether polyol oligomer, propylene oxide and ethylene oxide in the intermediate solution was 1:1.31:0.48 when mixed. The polymerization reaction was carried out by stirring and heating for 3.5 hours under the reaction conditions of 138° C. and 0.19 MPa. After the polymerization reaction was completed, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.098 MPa and maintained for 1.2 hours to remove unreacted monomers. The material was discharged after the temperature in the polymerization reactor dropped to 78° C. to obtain a polyether polyol. Step (3), glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol are mixed uniformly to obtain a polyester raw material solution, wherein the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is 1:0.945:0.415; the polyester raw material solution is added to an esterification reaction kettle, and heated at 98 Nm 3 Nitrogen was introduced into the esterification reaction kettle at a flow rate of / h until the oxygen content in the esterification reaction kettle reached 42ppm, thus completing the nitrogen replacement; After nitrogen replacement is completed, adjust the nitrogen flow rate to 18Nm 3 / h, then heating the polyester raw material solution to 158°C at a heating rate of 9.5°C / min and keeping the temperature for reaction for 1.8h, then continuing to heat to 188°C at a heating rate of 4.5°C / min and keeping the temperature for esterification reaction, distilling the water generated by the reaction during the esterification reaction, and when the acid value of the reaction product generated by the esterification reaction drops below 20mgKOH / g, sending the reaction product generated by the esterification reaction into a flash evaporator for flash evaporation, the flash evaporation temperature is 245°C, the flash evaporation pressure is 12kPa, and the esterification product is obtained after the flash evaporation; Then, with 18Nm 3 / h flow rate into the polycondensation reaction kettle, transfer the esterification product to the polycondensation reaction kettle, add dibutyltin dilaurate to the esterification product, the amount of dibutyltin dilaurate added is 0.21% of the mass of glutaric acid, and mix well to obtain a reaction precursor solution; then, stop passing nitrogen into the polycondensation reaction kettle, and evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches -0.028MPa, after the pressure in the polycondensation reaction kettle stabilizes, heat the reaction precursor solution to 208°C at a heating rate of 4.5°C / min and keep it warm for reaction for 1.2h; then, continue to evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches -0.088MPa, after the pressure in the polycondensation reaction kettle stabilizes, continue to heat the reaction precursor solution to 238°C at a heating rate of 2.8°C / min and keep it warm for reaction for 3.5h, and after the insulation is completed, obtain polyester polyol; Step (4), the polyether polyol prepared in step (2) and the polyester polyol prepared in step (3) are mixed uniformly at a mass ratio of 4.8:1, and dehydrated at -0.093 MPa and 108°C for 1.2 hours to obtain component A with a water content of 0.04%; isophorone diisocyanate is used as component B; 1,4-butanediol is dehydrated at -0.093 MPa and 108°C for 1.2 hours to obtain 1,4-butanediol with a water content of 0.04%, and the dehydrated 1,4-butanediol and triethylamine are mixed uniformly at a mass ratio of 1:0.045 to obtain component C; Component A at 88°C, component B at 48°C and component C at 88°C are mixed evenly in a mass ratio of 1:0.28:0.08 and injected into a mold at 98°C. The mixture is demolded after cooling and finally heated for vulcanization at a temperature of 92°C and a time of 12.5 hours. After the vulcanization is completed, the transparent grade thermoplastic polyurethane elastomer is obtained.
[0128] Example 5 This embodiment provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, such as Figure 1 As shown, the preparation method comprises: Step (1), dissolving anhydrous zinc chloride with a concentration of 0.4 g / mL in deionized water to obtain a zinc chloride solution, adding a dilute hydrochloric acid solution with a concentration of 0.3 mol / L to the zinc chloride solution, wherein the mixing ratio of anhydrous zinc chloride to the dilute hydrochloric acid solution in the zinc chloride solution is 10 g:0.5 mL, and mixing well to obtain a zinc chloride acid solution; Tetramethylethylenediamine was added to the zinc chloride acid solution under stirring, the mass ratio of anhydrous zinc chloride in the zinc chloride acid solution to tetramethyldiethylamine was 1:3, and the reaction solution was obtained after mixing for 24 hours; a potassium ferrocyanide solution with a mass fraction of 10wt% was added dropwise to the reaction solution, the molar ratio of zinc ions in the reaction solution to iron ions in the potassium ferrocyanide solution was 3.2:1, and after all the potassium ferrocyanide solution was added dropwise, the formed mixed solution was stirred for 24 hours to react, and after the reaction was completed, the solution was filtered, and then the solid product obtained by filtration was washed 5 times with deionized water, and then washed 5 times with tert-butyl alcohol, and after the washing was completed, it was placed in a vacuum dryer at 85°C for 12 hours to obtain a reaction product; The reaction product and tert-butanol were mixed evenly in a mixing ratio of 1 g:5 mL, and heated under a nitrogen atmosphere and 85° C. for 40 h to react. After the reaction was completed, the solid product was filtered, and then washed 5 times with deionized water and then washed 5 times with tert-butanol. After washing, the solid product was placed under vacuum drying at 85° C. for 12 h to obtain a white powdery cyanide complex. Step (2), castor oil, bisphenol A and potassium hydroxide are mixed uniformly in a mass ratio of 100:60:1.5 to obtain a polyether raw material solution, and the polyether raw material solution is added to a polymerization reactor at 100 Nm 3 Nitrogen was introduced into the polymerization reactor at a flow rate of 80 Nm / h until the oxygen content in the polymerization reactor reached 40 ppm, thus completing nitrogen replacement. The polyether raw material solution was then heated to 110°C, and nitrogen was introduced into the polyether raw material solution from the bottom of the polymerization reactor at a flow rate of 80 Nm / h. 3 / h flow rate of nitrogen, at the same time, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.1MPa and maintained for 1h, to complete nitrogen bubbling decompression dehydration, the water content of the polyether raw material solution after dehydration was 0.15%; Subsequently, the temperature in the polymerization reactor was adjusted to 100° C., and the pressure was adjusted to 0.18 MPa. Propylene oxide was added to the polyether raw material solution. The ratio of the total mass of castor oil and bisphenol A in the polyether raw material solution to the mass of propylene oxide was 10:1. The reaction was stirred and heated for 0.5 h under the reaction conditions of 100° C. and 0.18 MPa. The reaction was then heated to 130° C. at a heating rate of 3° C. / min and kept warm for 2 h. When the pressure in the polymerization reactor continued to decrease and dropped to negative pressure, and the temperature began to continue to rise, it indicated that the induction reaction was completed, and a polyether polyol oligomer was obtained. Adding the cyanide complex and phosphoric acid solution prepared in step (1) to the polyether polyol oligomer, wherein the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is 1000:0.12:0.009, and the mass fraction of the phosphoric acid solution is 90wt%, and mixing them uniformly to obtain an intermediate solution; The temperature in the polymerization reactor was adjusted to 140° C., and the pressure was adjusted to 0.18 MPa. Propylene oxide and ethylene oxide were added to the intermediate solution. The mass ratio of the polyether polyol oligomer, propylene oxide and ethylene oxide in the intermediate solution was 1:1.32:0.5 when mixed. The polymerization reaction was carried out by stirring and heating for 3 hours under the reaction conditions of 140° C. and 0.18 MPa. After the polymerization reaction was completed, the polymerization reactor was evacuated until the vacuum degree in the polymerization reactor reached -0.1 MPa and maintained for 1 hour to remove unreacted monomers. After the temperature in the polymerization reactor dropped to 80° C., the material was discharged to obtain a polyether polyol. Step (3), glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol are mixed uniformly to obtain a polyester raw material solution, wherein the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is 1:0.95:0.42; the polyester raw material solution is added to an esterification reaction kettle and heated at 100 Nm 3 Nitrogen was introduced into the esterification reaction kettle at a flow rate of / h until the oxygen content in the esterification reaction kettle reached 40ppm, thus completing the nitrogen replacement; After nitrogen replacement is completed, adjust the nitrogen flow rate to 20Nm 3 / h, then heating the polyester raw material solution to 160°C at a heating rate of 10°C / min and keeping the temperature for reaction for 1.5h, then continuing to heat to 190°C at a heating rate of 5°C / min and keeping the temperature for esterification reaction, distilling the water generated by the reaction during the esterification reaction, and when the acid value of the reaction product generated by the esterification reaction drops below 20mgKOH / g, sending the reaction product generated by the esterification reaction into a flash evaporator for flash evaporation, the flash evaporation temperature is 250°C, the flash evaporation pressure is 10kPa, and the esterification product is obtained after the flash evaporation; Then, at 20Nm 3 / h flow rate into the polycondensation reaction kettle, transfer the esterification product to the polycondensation reaction kettle, add dibutyltin dilaurate to the esterification product, the amount of dibutyltin dilaurate added is 0.23% of the mass of glutaric acid, and mix well to obtain a reaction precursor solution; then, stop passing nitrogen into the polycondensation reaction kettle, and evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches -0.03MPa, after the pressure in the polycondensation reaction kettle is stable, heat the reaction precursor solution to 210°C at a heating rate of 5°C / min and keep it warm for reaction for 1h; then, continue to evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches -0.09MPa, after the pressure in the polycondensation reaction kettle is stable, continue to heat the reaction precursor solution to 240°C at a heating rate of 3°C / min and keep it warm for reaction for 3h, and obtain polyester polyol after the insulation ends; Step (4), the polyether polyol prepared in step (2) and the polyester polyol prepared in step (3) are mixed uniformly at a mass ratio of 5:1, and dehydrated at -0.095 MPa and 110° C. for 1 h to obtain component A with a water content of 0.05%; isophorone diisocyanate is used as component B; 1,4-butanediol is dehydrated at -0.095 MPa and 110° C. for 1 h to obtain 1,4-butanediol with a water content of 0.05%, and the dehydrated 1,4-butanediol and dimethylaminoethyl ether are mixed uniformly at a mass ratio of 1:0.05 to obtain component C; Component A at 90°C, component B at 50°C and component C at 90°C are mixed evenly in a mass ratio of 1:0.3:0.1 and injected into a mold at 100°C. The mixture is demolded after cooling and finally heated for vulcanization at a temperature of 95°C and a vulcanization time of 12 hours. After the vulcanization is completed, the transparent grade thermoplastic polyurethane elastomer is obtained.
[0129] Comparative Example 1 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer. The difference from Example 1 is that in step (2), the ratio of the total mass of castor oil and bisphenol A in the polyether raw material solution to the mass of propylene oxide is adjusted to 5:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0130] Comparative Example 2 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, which differs from Example 1 in that, in step (2), the mass ratio of the total mass of castor oil and bisphenol A in the polyether raw material solution to the mass of propylene oxide is adjusted to 12:1, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0131] Comparative Example 3 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, which differs from Example 1 in that in step (2), the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is adjusted to 1000:0.08:0.008, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0132] Comparative Example 4 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, which differs from Example 1 in that in step (2), the mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is adjusted to 1000:0.15:0.008, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0133] Comparative Example 5 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, which differs from Example 1 in that in step (3), the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is adjusted to 1:0.93:0.35, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0134] Comparative Example 6 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, which differs from Example 1 in that in step (3), the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is adjusted to 1:0.93:0.45, and the other process parameters and operating steps are exactly the same as those in Example 1.
[0135] Comparative Example 7 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer. The difference from Example 1 is that in step (4), the mass ratio of polyether polyol to polyester polyol is adjusted to 3:1, and the other process parameters and operation steps are exactly the same as those in Example 1.
[0136] Comparative Example 8 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer. The difference from Example 1 is that in step (4), the mass ratio of polyether polyol to polyester polyol is adjusted to 6:1, and the other process parameters and operation steps are exactly the same as those in Example 1.
[0137] Comparative Example 9 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer. The difference from Example 1 is that in step (4), the mass ratio of component A, component B and component C when mixed is 1:0.15:0.05, and the other process parameters and operation steps are exactly the same as those in Example 1.
[0138] Comparative Example 10 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer. The difference from Example 1 is that in step (4), the mass ratio of component A, component B and component C when mixed is 1:0.35:0.05, and the other process parameters and operation steps are exactly the same as those in Example 1.
[0139] Comparative Example 11 This comparative example provides a method for preparing a transparent grade thermoplastic polyurethane elastomer, which differs from Example 1 in that, in step (1), tetramethylethylenediamine is not added to the zinc chloride acid solution, and a potassium ferrocyanide solution with a mass fraction of 8 wt% is directly added dropwise to the zinc chloride acid solution. The other process parameters and operating steps are exactly the same as those in Example 1.
[0140] Figure 32 are XRD spectra of the cyanide complexes prepared in Example 1 and Comparative Example 11. It can be seen from the figure that the addition of the chelating agent tetramethylethylenediamine affects the crystallinity of the DMC catalyst. Compared with Comparative Example 11, the XRD spectrum of Example 1 only has two diffraction peaks at 2θ of 18.7° and 23.4°, which indicates that the crystallinity of the DMC catalyst prepared in Example 1 is lower than that of Comparative Example 11. This is because the addition of tetramethylethylenediamine can effectively destroy the crystallinity of the cyanide complex molecules, and the increase in non-crystallinity can make propylene oxide and ethylene oxide more easily penetrate into the structure of the DMC catalyst, thereby promoting the ring-opening polymerization of propylene oxide and ethylene oxide.
[0141] Figure 4 and Figure 5 The scanning electron microscope images of the cyanide complexes prepared in Example 1 of the present invention and Comparative Example 11 are shown respectively. It can be seen from the images that the cyanide complexes prepared in Example 1 and Comparative Example 11 present a stacked sheet structure. However, compared with Comparative Example 11, the cyanide complex prepared in Example 1 presents more fragmented small particles, thereby exposing more active sites, which is beneficial to improving the catalytic activity of the DMC catalyst.
[0142] The tensile strength, elongation at break, Shore hardness and light transmittance of the transparent grade thermoplastic polyurethane elastomers prepared in Examples 1 to 5 and Comparative Examples 1 to 11 were tested for performance, and the test standards used were as follows: (1) The tensile strength and elongation at break are tested in accordance with the current national standard GB / T528-2009 "Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber"; (2) Shore hardness is tested in accordance with the current national standard GB / T531.1-2008 "Test method for indentation hardness of vulcanized rubber or thermoplastic rubber Part 1: Shore durometer method (Shore hardness)"; (3) The light transmittance is tested in accordance with the current national standard GB / T2410-2008 “Determination of light transmittance and haze of transparent plastics”.
[0143] The test results are shown in Table 1.
[0144] Table 1 Performance test results of Examples 1 to 5 and Comparative Examples 1 to 11
[0145] It can be seen from the test data provided in Table 1 that the polyurethane elastomer prepared by the method for preparing a transparent grade thermoplastic polyurethane elastomer provided by the present invention has both excellent mechanical properties and optical transparency.
[0146] It can be seen from the test data of Example 1, Comparative Example 1 and Comparative Example 2 that the tensile strength, elongation at break, Shore hardness and light transmittance of the polyurethane elastomer prepared in Comparative Example 1 are basically the same as those in Example 1, but due to the excessive addition of propylene oxide in Comparative Example 1, the heat released by the reaction increases. Once the polymerization reaction starts, the subsequent chain reaction will continuously release a large amount of heat, which is prone to safety hazards. The tensile strength, elongation at break, Shore hardness and light transmittance of the polyurethane elastomer prepared in Comparative Example 2 are much lower than those in Example 1. This is because the amount of castor oil and bisphenol A used in Comparative Example 2 is too much, the amount of propylene oxide used is relatively too little, the concentration of propylene oxide monomer that triggers the induction reaction is too low, the induction reaction time is too long, and the catalyst is poisoned and deactivated, which affects the transparency and mechanical properties of the polyether polyol finally obtained.
[0147] It can be seen from the test data of Example 1, Comparative Example 3 and Comparative Example 4 that the tensile strength, elongation at break, Shore hardness and light transmittance of the polyurethane elastomer prepared in Comparative Example 3 are much lower than those in Example 1. This is because the amount of cyanide complex used in Comparative Example 3 is too small, resulting in incomplete copolymerization of propylene oxide and ethylene oxide, affecting the transparency and mechanical properties of the polyether polyol finally obtained. The light transmittance of the polyurethane elastomer prepared in Comparative Example 4 is much lower than that in Example 1. This is because the amount of cyanide complex used in Comparative Example 4 is too large, and the amount of polyether polyol oligomer used is relatively too small, resulting in the appearance of the obtained polyether polyol being pink, thereby affecting the transparency of the subsequently synthesized polyurethane elastomer.
[0148] It can be seen from the test data of Example 1, Comparative Example 5 and Comparative Example 6 that the light transmittance of the polyurethane elastomer prepared in Comparative Example 5 is much lower than that in Example 1, while the tensile strength and Shore hardness are slightly higher than those in Example 1. This is because the amount of 1,2-propylene glycol used in Comparative Example 5 is too small, and the amount of 1,3-propylene glycol used is relatively excessive. Since there is no side chain in the 1,3-propylene glycol molecule and the soft segment is relatively long, the molecules are easier to entangle with each other, and hydrogen bonds are easily formed between the molecules, which increases the intermolecular fluid dynamics volume and is easy to crystallize. The crystallinity of the generated polyester polyol will increase, resulting in improved mechanical properties, but decreased light transmittance. The tensile strength, elongation at break and Shore hardness of the polyurethane elastomer prepared in Comparative Example 6 are much lower than those in Example 1, while the transmittance is slightly higher than that in Example 1. This is because the amount of 1,2-propylene glycol used in Comparative Example 6 is too much, while the amount of 1,3-propylene glycol used is relatively too little. Since 1,2-propylene glycol contains side chains, the formation of hydrogen bonds between polyester polyol molecules is hindered, thereby affecting the crystallization properties of polyester polyols. The crystallinity of the generated polyester polyols will decrease, resulting in reduced mechanical properties, but improved transmittance.
[0149] It can be seen from the test data of Example 1, Comparative Example 7 and Comparative Example 8 that the elongation at break of the polyurethane elastomer prepared in Comparative Example 7 is much lower than that in Example 1. This is because the amount of polyether polyol used in Comparative Example 7 is too small, and the amount of polyester polyol used is relatively too large. Since the ester group in the polyester polyol has a large polarity and a strong intermolecular force, the addition of polyester polyol promotes the improvement of the strength of the polyurethane elastomer. However, due to the poor flexibility of the polyester polyol molecular chain, its excessive addition will cause the elongation at break of the polyurethane elastomer to be significantly reduced. The tensile strength and Shore hardness of the polyurethane elastomer prepared in Comparative Example 8 are much lower than those in Example 1. This is because the amount of polyether polyol used in Comparative Example 8 is too large, and the amount of polyester polyol used is relatively small, and its mechanical reinforcement effect cannot be exerted.
[0150] It can be seen from the test data of Example 1, Comparative Example 9 and Comparative Example 10 that the tensile strength and Shore hardness of the polyurethane elastomer prepared in Comparative Example 9 are much lower than those in Example 1. This is because the amount of component B in Comparative Example 9 is too small and the amount of component A is relatively too large, which means that the content of soft segments in the synthesized polyurethane elastomer is increased, and relatively, the content of hard segments is decreased, which is not conducive to the formation of hydrogen bonds between hard segments, and the degree of microphase separation is reduced, thereby resulting in a decrease in the strength and hardness of the polyurethane elastomer. The elongation at break of the polyurethane elastomer prepared in Comparative Example 10 is much lower than that in Example 1, while the tensile strength and Shore hardness are slightly higher than those in Example 1. This is because the amount of component B in Comparative Example 10 is too large and the amount of component A is relatively too small, the content of hard segments in the synthesized polyurethane elastomer is increased, the hydrogen bonding force between molecules is enhanced, and the strength and hardness of the polyurethane elastomer are increased, but the elongation at break is decreased.
[0151] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a transparent grade thermoplastic polyurethane elastomer, characterized in that: The preparation method comprises: Step (I), mixing castor oil, bisphenol A and potassium hydroxide uniformly to obtain a polyether raw material solution, adding the polyether raw material solution into a polymerization reactor, replacing the polymerization reactor with nitrogen and decompressing and dehydrating the polyether raw material solution by nitrogen bubbling, then adjusting the temperature and pressure in the polymerization reactor, adding propylene oxide to the polyether raw material solution, stirring and heating to induce a reaction, and obtaining a polyether polyol oligomer; adding a cyanide complex and a phosphoric acid solution to the polyether polyol oligomer, mixing uniformly to obtain an intermediate solution; adjusting the temperature and pressure in the polymerization reactor, adding propylene oxide and ethylene oxide to the intermediate solution, stirring and heating to perform a polymerization reaction, and obtaining a polyether polyol; Step (II), glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol are mixed uniformly to obtain a polyester raw material solution, the polyester raw material solution is added to an esterification reaction kettle, the esterification reaction kettle is replaced with nitrogen, and then the polyester raw material solution is stirred and heated to cause an esterification reaction; after the esterification reaction is completed, the esterification product obtained by the reaction is transferred to a polycondensation reaction kettle, dibutyltin dilaurate is added to the esterification product, and the mixture is stirred and heated to cause a polycondensation reaction, and a polyester polyol is obtained after the reaction is completed; Step (III), the polyether polyol prepared in step (I) and the polyester polyol prepared in step (II) are mixed evenly, and dehydrated under vacuum and heating conditions to obtain component A; aliphatic isocyanate is used as component B; the dehydrated 1,4-butanediol and a tertiary amine catalyst are mixed evenly to obtain component C; the component A, the component B and the component C are mixed evenly and then injected into a mold, demolded after cooling, and finally heated and vulcanized to obtain a transparent grade thermoplastic polyurethane elastomer.
2. The method for preparing a transparent grade thermoplastic polyurethane elastomer according to claim 1, characterized in that: In step (I), the mass ratio of the castor oil, the bisphenol A and the potassium hydroxide is 100:(50-60):(1.2-1.5); The operation process of nitrogen replacement of the polymerization reactor comprises: 90~100Nm 3 / h, introducing nitrogen into the polymerization reactor until the oxygen content in the polymerization reactor is ≤50ppm; The operation process of nitrogen bubbling decompression dehydration of the polyether raw material solution comprises: The polyether raw material solution is heated to a dehydration temperature, and nitrogen is bubbled into the polyether raw material solution from the bottom of the polymerization reactor, and the polymerization reactor is evacuated to a negative pressure to perform nitrogen bubbling decompression dehydration; The dehydration temperature is 100-110°C; The flow rate of nitrogen gas injected into the polyether raw material solution is 60-80 Nm 3 / h; The vacuum degree in the polymerization reactor after evacuation is controlled at -0.09 to -0.1 MPa; The nitrogen bubbling decompression dehydration time is 1 to 2 hours; The water content of the polyether raw material solution after nitrogen bubbling and reduced pressure dehydration is ≤0.15%.
3. The method for preparing a transparent grade thermoplastic polyurethane elastomer according to claim 1, characterized in that: In step (I), before adding propylene oxide to the polyether raw material solution, the temperature in the polymerization reactor is adjusted to 90-100° C.; Before adding propylene oxide to the polyether raw material solution, adjusting the pressure in the polymerization reactor to 0.18-0.23 MPa; The ratio of the total mass of castor oil and bisphenol A in the polyether raw material solution to the mass of propylene oxide is (8-10):1; The operation process of the induction reaction includes: After adding propylene oxide to the polyether raw material solution, the solution is kept warm for reaction, and then the temperature is increased to an induction temperature at a first heating rate and kept warm for reaction, when the pressure in the polymerization reactor continues to decrease and drops to a negative pressure, and the temperature begins to rise continuously, indicating that the induction reaction is completed, and the polyether polyol oligomer is obtained; Add propylene oxide to the polyether raw material solution and keep the temperature to react for 0.5 to 1 hour; The first heating rate is 1-3°C / min; The induction temperature is 120-130°C; Keep the reaction at the induction temperature for 2 to 3 hours; The mass ratio of the polyether polyol oligomer, the cyanide complex and the phosphoric acid solution is 1000:(0.1-0.12):(0.008-0.009); The mass fraction of the phosphoric acid solution is 80-90wt%; Before adding propylene oxide and ethylene oxide to the intermediate solution, adjusting the temperature in the polymerization reactor to 130-140° C.; Before adding propylene oxide and ethylene oxide to the intermediate solution, adjusting the pressure in the polymerization reactor to 0.18-0.23 MPa; The mass ratio of the polyether polyol oligomer, propylene oxide and ethylene oxide when mixed in the intermediate solution is 1:(1.28-1.32):(0.4-0.5); The polymerization reaction time is 3 to 5 hours; After the polymerization reaction is completed, the polymerization reactor is evacuated until the vacuum degree in the polymerization reactor reaches -0.09~-0.1MPa, and maintained for 1~2h to remove unreacted monomers, and the material is discharged after the temperature in the polymerization reactor drops to 70~80°C.
4. The method for preparing a transparent grade thermoplastic polyurethane elastomer according to claim 1, characterized in that: In step (I), the cyanide complex is prepared by the following method: Anhydrous zinc chloride is dissolved in deionized water to obtain a zinc chloride solution, and a dilute hydrochloric acid solution is added to the zinc chloride solution to obtain a zinc chloride acid solution; tetramethylethylenediamine is added to the zinc chloride acid solution under stirring conditions, and the mixture is mixed to obtain a reaction solution; potassium ferrocyanide solution is added dropwise to the reaction solution, and the mixture is mixed and stirred to react, and after the reaction is completed, the mixture is filtered, washed, and dried to obtain a reaction product; the reaction product is mixed evenly with tert-butyl alcohol, and the mixture is heated under a nitrogen atmosphere to react, and after the reaction is completed, the mixture is filtered, washed, and dried to obtain a white powdery cyanide complex.
5. The method for preparing a transparent grade thermoplastic polyurethane elastomer according to claim 4, characterized in that: The concentration of anhydrous zinc chloride in the zinc chloride solution is 0.3-0.4 g / mL; The mixing ratio of anhydrous zinc chloride in the zinc chloride solution and the dilute hydrochloric acid solution is 10 g: (0.1-0.5) mL; The concentration of the dilute hydrochloric acid solution is 0.1-0.3 mol / L; The mass ratio of anhydrous zinc chloride in the zinc chloride acid solution to the tetramethyl diethylamine is 1:(2-3); The mixing time of the zinc chloride acid solution and the tetramethylethylenediamine is 12 to 24 hours; The mass fraction of the potassium ferrocyanide solution is 8-10wt%; The molar ratio of zinc ions in the reaction solution to iron ions in the potassium ferrocyanide solution is (2.8-3.2):1; After the potassium ferrocyanide solution is completely added, the formed mixed solution is stirred for 12 to 24 hours; The mixing ratio of the reaction product and tert-butyl alcohol is 1 g: (3-5) mL; The heating temperature after the reaction product and tert-butyl alcohol are mixed is 75-85°C; The heating time after the reaction product and tert-butyl alcohol are mixed is 40 to 50 hours; The washing process comprises: washing with deionized water for 3 to 5 times, and then washing with tert-butyl alcohol for 3 to 5 times; The drying temperature is 75-85°C; The drying time is 12 to 24 hours.
6. The method for preparing a transparent grade thermoplastic polyurethane elastomer according to claim 1, characterized in that: In step (II), the molar ratio of glutaric acid, 1,3-propylene glycol and 1,2-propylene glycol is 1:(0.93-0.95):(0.4-0.42); The operation process of nitrogen replacement of the esterification reactor includes: 90~100Nm 3 / h into the esterification reaction kettle until the oxygen content in the esterification reaction kettle is ≤50ppm; The operation process of the esterification reaction comprises: After the nitrogen replacement of the esterification reaction kettle is completed, the flow rate of nitrogen is lowered, and then the polyester raw material solution is heated to the first esterification temperature at a second heating rate and kept warm for reaction, and then continued to be heated to the second esterification temperature at a third heating rate and kept warm for reaction, so as to carry out the esterification reaction, and the water generated by the reaction is evaporated during the esterification reaction. When the acid value of the reaction product generated by the esterification reaction drops to less than 20 mgKOH / g, the reaction product generated by the esterification reaction is sent to a flash evaporator for flash evaporation, and an esterification product is obtained after the flash evaporation is completed; After the nitrogen replacement of the esterification reactor is completed, the nitrogen flow rate is adjusted to 10~20Nm 3 / h; The second heating rate is 8-10°C / min; The first esterification temperature is 150-160°C; Keep the reaction at the first esterification temperature for 1.5 to 2.5 hours; The third heating rate is 3-5°C / min; The second esterification temperature is 180-190°C; The flash evaporation temperature is 230-250°C; The flash evaporation pressure is 10-20 kPa.
7. The method for preparing a transparent grade thermoplastic polyurethane elastomer according to claim 1, characterized in that: In step (II), the polycondensation reaction process includes: Continuously introducing nitrogen into the polycondensation reaction kettle, transferring the esterification product into the polycondensation reaction kettle, adding the dibutyltin dilaurate into the esterification product, and obtaining a reaction precursor solution; subsequently, stopping introducing nitrogen into the polycondensation reaction kettle, and evacuating the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches a first vacuum degree, and after the pressure in the polycondensation reaction kettle is stabilized, heating the reaction precursor solution to a first polycondensation temperature at a fourth heating rate and keeping the temperature for reaction; subsequently, continuing to evacuate the polycondensation reaction kettle until the pressure in the polycondensation reaction kettle reaches a second vacuum degree, and after the pressure in the polycondensation reaction kettle is stabilized, continuing to heat the reaction precursor solution to a second polycondensation temperature at a fifth heating rate and keeping the temperature for reaction, and obtaining the polyester polyol after the insulation is completed; The flow rate of nitrogen introduced into the polycondensation reactor is 10~20Nm 3 / h; The amount of dibutyltin dilaurate added is 0.18-0.23% of the mass of glutaric acid; The first vacuum degree is -0.02~-0.03MPa; The fourth heating rate is 3-5°C / min; The first polycondensation temperature is 200-210°C; Keep the reaction at the first polycondensation temperature for 1 to 2 hours; The second vacuum degree is -0.08~-0.09MPa; The fifth heating rate is 2-3°C / min; The second polycondensation temperature is 230-240°C; The reaction is maintained at the second polycondensation temperature for 3 to 5 hours.
8. The method for preparing a transparent grade thermoplastic polyurethane elastomer according to claim 1, characterized in that: In step (III), the mass ratio of the polyether polyol to the polyester polyol is (4-5):1; The vacuum degree of the polyether polyol and polyester polyol during dehydration is -0.09 to -0.095 MPa; The heating temperature of the polyether polyol and polyester polyol during dehydration is 100-110°C; The dehydration time of the polyether polyol and polyester polyol is 1 to 2 hours; The moisture content of the polyether polyol and polyester polyol after dehydration is ≤0.05%; The vacuum degree of the 1,4-butanediol during dehydration is -0.09 to -0.095 MPa; The heating temperature of the 1,4-butanediol during dehydration is 100-110°C; The dehydration time of the 1,4-butanediol is 1 to 2 hours; The moisture content of the 1,4-butanediol after dehydration is ≤0.05%; The mass ratio of the 1,4-butanediol to the tertiary amine catalyst is 1:(0.03-0.05); The tertiary amine catalyst includes any one of pentamethyldiethylenetriamine, N,N-dimethylcyclohexylamine, triethylenediamine, triethylamine or bis(dimethylamino)ethyl ether, or a combination of at least two thereof; The aliphatic isocyanate includes hexamethylene diisocyanate and / or isophorone diisocyanate.
9. The method for preparing a transparent grade thermoplastic polyurethane elastomer according to claim 1, characterized in that: In step (III), before the A component, the B component and the C component are mixed, the temperature of the A component and the C component is controlled at 80-90° C., and the temperature of the B component is controlled at 40-50° C.; The mass ratio of the A component, the B component and the C component when mixed is 1:(0.2-0.3):(0.05-0.1); The temperature of the mold is 90-100°C; The vulcanization temperature is 85-95°C; The vulcanization time is 12 to 14 hours.
10. A transparent grade thermoplastic polyurethane elastomer prepared by the method for preparing a transparent grade thermoplastic polyurethane elastomer according to any one of claims 1 to 9.
Citation Information
Patent Citations
Transparent high-elasticity thermoplastic polyurethane and method of producing the same
CN101402719A
Method for synthesizing high molecular weight castor oil polyether polyol
CN102532513A
High-transparency thermoplastic polyurethane elastomer and preparation method thereof
CN108559058A
Polyether polyol, preparation method thereof, and polyurethane foam
CN110054767A
Transparent non-yellowing thermoplastic polyurethane elastomer and preparation method thereof
CN115850644A
Cited By
Molecular sieve composite catalyst as well as preparation method and application thereof
CN115746235A
Molecular sieve composite catalyst and its preparation method and application
CN115746235B
